Method for producing molybdenum sulfide powder
By preparing molybdenum sulfide powder containing molybdenum disulfide 3R crystal structure, the problems of poor performance of molybdenum sulfide catalysts, poor adsorption performance of adsorbents and unsatisfactory light absorption performance of photothermal conversion materials in the prior art are solved, and the performance improvement of catalysts, adsorbents and photothermal conversion materials are achieved.
Patent Information
- Application Number
- CN202080066331.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-24
- Filing Date
- 2020-09-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-09-24
AI Technical Summary
It is difficult to effectively produce molybdenum sulfides with excellent catalyst performance in the prior art, and the adsorption properties of existing adsorbents are poor in heavy metals, and the light absorption properties of photothermal conversion materials are not satisfactory.
By preparing molybdenum sulfide powder containing 3R crystal structure of molybdenum disulfide, and using a specific heat treatment method, a catalyst with excellent oxygen reduction reaction activity, a heavy metal adsorbent and a high-efficiency photothermal conversion material with high adsorption properties are produced.
The excellent oxygen reduction reaction performance of the catalyst is achieved, the adsorption performance of heavy metals is improved, and the light absorption performance of the photothermal conversion material is significantly improved.
Smart Images

Figure CN114423714B_ABST
Abstract
Description
[0001] This application claims priority based on international application PCT / JP2019 / 037236 filed with the Japan Patent Office on September 24, 2019, the contents of which are incorporated herein. Technical Field
[0002] The present invention relates to a molybdenum sulfide powder and a method for preparing the same, an oxygen reduction catalyst and a catalyst ink. In addition, the present invention relates to an adsorbent containing molybdenum sulfide particles. Furthermore, the present invention relates to a photothermal conversion material containing a material containing molybdenum sulfide particles and a distillation method using the same. Background Art
[0003] Molybdenum sulfides represented by molybdenum disulfide (MoS2) are widely known as lubricants, steel additives, and molybdate raw materials. These molybdenum sulfides have been used for applications that effectively utilize the advantages of inertness.
[0004] However, recently, with an eye on its activity, attempts have been made to apply it to fine applications such as semiconductor materials and catalysts. By miniaturizing or releasing the aggregation of molybdenum sulfide obtained by any manufacturing method such as sulfiding molybdenum oxide, such activity can be improved to some extent, but these alone often do not provide the expected excellent performance. Therefore, in order to achieve better performance according to the respective purposes of use, methods for producing molybdenum sulfide in special shapes such as monolayer, nanoflower, and fullerene are being studied (see Patent Documents 1 to 2).
[0005] Previously, zeolite-based adsorbents and titanosilicate-based adsorbents have been known as heavy metal adsorbents for water purification materials (Patent Document 3, etc.) These adsorbents are considered to have excellent adsorption performance for heavy metals such as lead.
[0006] In addition, instead of generating electricity directly from sunlight, various devices are known that use sunlight to heat a fluid and temporarily store the heat there to generate steam, and then transport the heat to other places or directly store it for later use, and also generate electricity from electricity to hot water supply equipment for general household use.
[0007] For example, Patent Document 4 proposes a solar heat collection method in which a dispersion of nanoparticles of metal or metal oxide is exposed to sunlight and the sunlight is converted into heat energy in the nanoparticle dispersion.
[0008] In addition, Patent Document 5 proposes a solar light absorbing fluid and a distillation method using the same, wherein the solar light absorbing fluid is a fluid in which titanium nitride nanoparticles are dispersed in a liquid, and absorbs and accumulates the irradiated light energy. Distillation requires evaporation of the liquid, and thus requires a large amount of energy. If all or part of the energy can be supplied by sunlight, it is effective for energy saving.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2004-277199
[0012] Patent Document 2: Japanese Patent Publication No. 2004-512250
[0013] Patent Document 3: International Publication No. 2004 / 039494
[0014] Patent Document 4: Japanese Patent Application Publication No. 2010-144957
[0015] Patent Document 5: Japanese Patent Application Publication No. 2016-125679 Summary of the invention
[0016] Problems to be solved by the invention
[0017] However, the methods for producing molybdenum sulfide with a specific shape disclosed in Patent Documents 1 and 2 are all complicated, and it is difficult to obtain the molybdenum sulfide as described. In the case of the successful experiments in the known documents, even if the molybdenum sulfide obtained was finely divided into particles in the electron microscope photograph, it was actually seriously agglomerated, and the expected catalyst performance was not obtained.
[0018] The zeolite-based adsorbent disclosed in Patent Document 3 adsorbs mineral components such as K and Ca, and is therefore not suitable for use as a water purification material. Titanosilicate-based adsorbents are expensive.
[0019] Patent Document 4 shows that nanoparticles of a single substance or an oxide of any metal type can be used, but does not disclose any specific knowledge on the selection of materials for nanoparticles of metal or metal oxide to be used.
[0020] In addition, the light absorption performance of the fluid in which titanium nitride nanoparticles are dispersed disclosed in Patent Document 5 is also unsatisfactory. In addition, gold, carbon nanotubes, etc., which are known as sunlight absorbing materials, are expensive. Carbon black has poor dispersibility in water and aggregates over time, and its sunlight absorption performance cannot be fully exerted.
[0021] Therefore, an object of the present invention is to provide a molybdenum sulfide powder having excellent catalytic activity, especially oxygen reduction reaction (ORR) activity, and a method for producing the same, an oxygen reduction catalyst, and a catalyst ink.
[0022] Another object of the present invention is to provide a heavy metal adsorbent having a selective adsorption performance that has a large adsorption performance for heavy metals and a small adsorption capacity for mineral components.
[0023] Furthermore, an object of the present invention is to provide a photothermal conversion material and a distillation method having excellent light absorption performance.
[0024] Technical means of solving problems
[0025] The present invention includes the following forms.
[0026] [1] A molybdenum sulfide powder comprising a 3R crystal structure of molybdenum disulfide.
[0027] [2] The molybdenum sulfide powder according to [1], comprising a 2H crystal structure and a 3R crystal structure of molybdenum disulfide.
[0028] [3] According to the molybdenum sulfide powder described in [2], in which, in the spectrum obtained by powder X-ray diffraction (X-Ray Diffraction, XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of 2H crystal structure and 3R crystal structure, and the half-value width is greater than 1°.
[0029] [4] The molybdenum sulfide powder according to any one of [1] to [3], wherein the specific surface area measured by the Brunauer-Emmett-Teller (BET) method is 10 m 2 / g or above.
[0030] [5] The molybdenum sulfide powder according to any one of [1] to [4], wherein the median particle size D 50 It is 10nm~1000nm.
[0031] [6] The molybdenum sulfide powder according to any one of [1] to [5], wherein in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo is greater than 1.0.
[0032] [7] The molybdenum sulfide powder according to any one of [1] to [6], wherein the primary particles of the molybdenum sulfide particles constituting the molybdenum sulfide powder are in the shape of ropes, belts or sheets.
[0033] [8] A method for producing molybdenum sulfide powder, wherein the molybdenum sulfide powder according to any one of [1] to [7] is produced, comprising: heating molybdenum trioxide powder at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure comprising molybdenum trioxide.
[0034] [9] A method for producing molybdenum sulfide powder, wherein the molybdenum sulfide powder according to any one of [1] to [7] is produced, comprising: heating molybdenum trioxide powder at a temperature of 100°C to 800°C in the absence of a sulfur source, and then heating the molybdenum trioxide powder at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure comprising molybdenum trioxide.
[0035]
[10] The method for producing molybdenum sulfide powder according to [8] or [9], wherein the average particle size of the primary particles of the molybdenum trioxide powder is 5 nm to 1000 nm.
[0036]
[11] A method for producing molybdenum sulfide powder according to any one of [8] to
[10] , wherein the amount of S in the sulfur source is 500 mol% or more relative to 100 mol% of MoO3 in the molybdenum trioxide powder.
[0037]
[12] The method for producing molybdenum sulfide powder according to any one of [8] to
[11] , wherein the heating temperature in the presence of the sulfur source is 320° C. or higher.
[0038]
[13] A heavy metal adsorbent, which is a heavy metal adsorbent containing molybdenum sulfide particles, wherein
[0039] The median particle size D of the molybdenum sulfide particles obtained by a dynamic light scattering particle size distribution analyzer is 50 It is 10nm~1000nm.
[0040]
[14] The heavy metal adsorbent according to
[13] , wherein the specific surface area of the molybdenum sulfide particles measured by the BET method is 10 m 2 / g or above.
[0041]
[15] A heavy metal adsorbent according to
[13] or
[14] , wherein in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the molybdenum sulfide particles at the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is greater than 1.0.
[0042]
[16] The heavy metal adsorbent according to any one of
[13] to
[15] , wherein the molybdenum sulfide particles contain a 3R crystal structure of molybdenum disulfide.
[0043]
[17] The heavy metal adsorbent according to
[16] , wherein the molybdenum sulfide particles contain a 2H crystal structure and a 3R crystal structure of molybdenum disulfide.
[0044]
[18] According to the heavy metal adsorbent described in
[17] , in the spectrum of the molybdenum sulfide particles obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of 2H crystal structure and 3R crystal structure, and the half-value width is greater than 1°.
[0045]
[19] The heavy metal adsorbent according to
[17] or
[18] , wherein the primary particles of the molybdenum sulfide particles are in the shape of ropes, belts or sheets.
[0046]
[20] A photothermal conversion material comprising a material containing molybdenum sulfide particles, which generates heat by absorbing light energy.
[0047]
[21] The photothermal conversion material according to
[20] , wherein the median particle size D of the molybdenum sulfide particles is determined by a dynamic light scattering particle size distribution measuring device. 50 It is 10nm~1000nm.
[0048]
[22] The photothermal conversion material according to
[20] or
[21] , wherein the specific surface area of the molybdenum sulfide particles measured by the BET method is 10 m 2 / g or above.
[0049]
[23] A photothermal conversion material according to any one of
[20] to
[22] , wherein in the radial distribution function of the molybdenum sulfide particles obtained by the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is greater than 1.0.
[0050]
[24] A photothermal conversion material according to any one of
[20] to
[23] , wherein the molybdenum sulfide particles comprise a 3R crystal structure of molybdenum disulfide.
[0051]
[25] The photothermal conversion material according to
[24] , wherein the molybdenum sulfide particles contain a 2H crystal structure and a 3R crystal structure of molybdenum disulfide.
[0052]
[26] According to the photothermal conversion material described in
[25] , in the spectrum of the molybdenum sulfide particles obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of 2H crystal structure and 3R crystal structure, and the half-value width is greater than 1°.
[0053]
[27] The photothermal conversion material according to
[24] or
[25] , wherein the primary particles of the molybdenum sulfide particles are in the shape of ropes, ribbons or sheets.
[0054]
[28] A photothermal conversion material according to any one of
[20] to
[27] , wherein the material containing the molybdenum sulfide particles is a light absorbing fluid containing a liquid and the molybdenum sulfide particles dispersed in the liquid.
[0055]
[29] The photothermal conversion material according to
[28] , wherein the main component of the liquid is water.
[0056]
[30] The photothermal conversion material according to
[28] or
[29] , wherein the molybdenum sulfide particles are contained in an amount of 0.01 mass % or more relative to the light absorbing fluid.
[0057]
[31] A distillation method, comprising irradiating the photothermal conversion material according to any one of
[28] to
[30] with sunlight to heat the material, thereby evaporating the liquid.
[0058]
[32] An oxygen reduction catalyst comprising molybdenum sulfide powder having a 3R crystal structure including molybdenum disulfide.
[0059]
[33] The oxygen reduction catalyst according to
[32] contains molybdenum sulfide powder having a 2H crystal structure and a 3R crystal structure of molybdenum disulfide.
[0060]
[34] According to the oxygen reduction catalyst described in
[33] , in the spectrum of the molybdenum sulfide powder obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of 2H crystal structure and 3R crystal structure, and the half-value width is greater than 1°.
[0061]
[35] The oxygen reduction catalyst according to any one of
[32] to
[34] , wherein the specific surface area of the molybdenum sulfide powder measured by the BET method is 10 m 2 / g or above.
[0062]
[36] The oxygen reduction catalyst according to any one of
[32] to
[35] , wherein the median particle size D of the molybdenum sulfide powder is determined by a dynamic light scattering particle size distribution analyzer. 50 It is 10nm~1000nm.
[0063]
[37] An oxygen reduction catalyst according to any one of
[32] to
[36] , wherein in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the molybdenum sulfide powder at the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo is greater than 1.0.
[0064]
[38] An oxygen reduction catalyst according to any one of
[32] to
[37] , wherein the primary particles of the molybdenum sulfide particles constituting the molybdenum sulfide powder are in the shape of ropes, belts or sheets.
[0065]
[39] A catalyst ink comprising the oxygen reduction catalyst according to any one of
[32] to
[38] , a polymer electrolyte and a solvent.
[0066] Effects of the Invention
[0067] According to the present invention, a molybdenum sulfide powder having excellent oxygen reduction reaction (ORR) activity, a method for producing the same, an oxygen reduction catalyst, and a catalyst ink can be provided.
[0068] Furthermore, according to the present invention, a heavy metal adsorbent having a selective adsorption performance with a large adsorption performance for heavy metals and a small adsorption capacity for mineral components can be provided.
[0069] Furthermore, according to the present invention, a photothermal conversion material and a distillation method having excellent light absorption performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a schematic diagram of an example of an apparatus used for producing molybdenum trioxide powder as a raw material.
[0071] Figure 2 This is a diagram showing the results of the X-ray diffraction (XRD) pattern of the molybdenum trioxide powder as a raw material, together with the standard pattern of the α crystal (α-MoO3) and the standard pattern of the β crystal (β-MoO3) of molybdenum trioxide.
[0072] Figure 3 This is a graph showing the results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of one embodiment of the present invention together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2).
[0073] Figure 4 The ORR current density (i / mAg) is expressed relative to the working voltage (vs RHE) of the working electrode obtained from MoS powder. -1 ) curve graph.
[0074] Figure 5 This is a diagram showing the results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of the comparative example together with the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2).
[0075] Figure 6 This is an extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption edge of molybdenum measured using molybdenum trioxide powder as a raw material.
[0076] Figure 7 This is a TEM image of the molybdenum sulfide powder according to one embodiment of the present invention.
[0077] Figure 8 These are TEM images of molybdenum sulfide powders of Examples and Comparative Examples.
[0078] Fig. 9 This is an extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption edge of molybdenum measured using the molybdenum sulfide powder according to one embodiment of the present invention.
[0079] Fig.10 It is a graph showing the results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Comparative Example 2 together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2).
[0080] Fig.11 It is a graph showing the results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Comparative Example 3 together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2).
[0081] Fig.12It is a graph showing the results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Comparative Example 4 together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2).
[0082] Fig.13 This is a graph showing the absorption spectra of the light absorbing fluids of the photothermal conversion materials of Examples and Comparative Examples at wavelengths from ultraviolet rays to near infrared rays together with the sunlight spectrum.
[0083] [Explanation of Symbols]
[0084] 1: Manufacturing device
[0085] 2: Calcination furnace
[0086] 3: Cooling piping
[0087] 4: Recycling Machine
[0088] 5: Exhaust port
[0089] 6: Opening adjustment damper
[0090] 7: Observation window
[0091] 8: Exhaust device DETAILED DESCRIPTION
[0092] <<Molybdenum sulfide powder>>
[0093] The molybdenum sulfide powder of the present embodiment includes the 3R crystal structure of molybdenum disulfide. In addition, the molybdenum sulfide powder of the present embodiment includes the 2H crystal structure and the 3R crystal structure of molybdenum disulfide, and in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, the peak near 39.5° and the peak near 49.5° both include the synthetic peak of the 2H crystal structure and the 3R crystal structure, and the half-value width is 1° or more. Furthermore, the molybdenum sulfide powder of the present embodiment may also include a crystal structure other than the 2H crystal structure and the 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.
[0094] The molybdenum sulfide particles constituting the molybdenum sulfide powder of the present embodiment include a 3R crystal structure of a metastable structure, and therefore have excellent oxygen reduction activity (ORR). The molybdenum sulfide particles constituting the molybdenum disulfide powder generally available on the market are molybdenum sulfide of a 2H crystal structure, whereas the molybdenum sulfide particles constituting the molybdenum sulfide powder of the present embodiment include a 3R crystal structure of a metastable structure, which can be distinguished by the fact that in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, the peak near 39.5° and the peak near 49.5° both include a synthetic peak of the 2H crystal structure and the 3R crystal structure.
[0095] In the molybdenum sulfide powder of the present embodiment, the shape of the primary particles of molybdenum sulfide in the two-dimensional image when the molybdenum sulfide particles constituting the molybdenum sulfide powder are photographed using a transmission electron microscope (TEM) can be particulate, spherical, plate-like, needle-like, rope-like, belt-like or sheet-like in visual observation or image photographs, and these shapes can also be included in combination. The shape of the primary particles of the molybdenum sulfide is preferably belt-like or sheet-like, and the shape of 50 primary particles of molybdenum sulfide is preferably on average having a length (vertical) × width (horizontal) = 50nm ~ 1000nm × 3 ~ 100nm range, more preferably having a size in the range of 100nm ~ 500nm × 5 ~ 50nm, and particularly preferably having a size in the range of 150nm ~ 400nm × 10 ~ 20nm. The shape of the primary particles of the molybdenum sulfide is preferably a size in the range of 1nm ~ 40nm in thickness, more preferably a size in the range of 3nm ~ 20nm, and particularly preferably a size in the range of 5nm ~ 10nm. Here, the so-called sheet shape refers to a thin layer shape. In addition, the so-called ribbon-like shape refers to a long thin layer shape. By being in a rope-like, ribbon-like or sheet-like shape, the specific surface area of the molybdenum sulfide powder can be increased, and the oxygen reduction reaction (ORR) activity can be excellent. Here, the so-called rope-like shape refers to a slender shape. The aspect ratio of the primary particles of the molybdenum sulfide, that is, the value of (length (longitudinal)) / (width (transverse)) is preferably 1.2 to 1200, more preferably 2 to 800, further preferably 5 to 400, and particularly preferably 10 to 200.
[0096] By making the primary particles of the molybdenum sulfide particles into ropes, belts or sheets with a large aspect ratio rather than simple spheres, the number of sites for adsorbing heavy metals increases, and the adsorption performance for heavy metals is excellent, especially the adsorption performance for heavy metals such as lead, mercury, silver and gold is significantly improved.
[0097] The specific surface area of the molybdenum sulfide powder of this embodiment measured by the BET method is preferably 10 m 2 / g or more, more preferably 30m 2 / g or more, particularly preferably 40 m 2 / g or more. The larger the specific surface area of the molybdenum sulfide powder of this embodiment, the better the oxygen reduction reaction (ORR) activity can be. The specific surface area of the molybdenum sulfide powder of this embodiment measured by the BET method can be 300m 2 / g or less, also 200m 2 / g or less, also 100m 2 / g or less.
[0098] The median diameter D of the molybdenum sulfide particles constituting the molybdenum sulfide powder of the present embodiment, as determined by a dynamic light scattering particle size distribution analyzer, is 50 The median particle size D of the molybdenum sulfide particles constituting the molybdenum sulfide powder of the present embodiment is preferably 10 nm to 1000 nm. In terms of a large surface area and reactivity with sulfur, the median particle size D is preferably 600 nm or less, more preferably 500 nm or less, and particularly preferably 400 nm or less. 50 The thickness may be greater than 10 nm, greater than 20 nm, or greater than 40 nm.
[0099] In the radial distribution function obtained by the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum of the molybdenum sulfide powder of this embodiment, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.
[0100] The conversion rate R of the molybdenum sulfide powder to MoS2 in this embodiment is C It is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more.
[0101] The molybdenum sulfide powder of this embodiment is converted into MoS2 by the conversion rate R C Large, can make the oxygen reduction reaction (ORR) activity excellent.
[0102] Conversion rate of molybdenum sulfide powder to MoS2 C It can be obtained by the reference intensity ratio (RIR) method based on the spectral data obtained by X-ray diffraction (XRD) measurement of molybdenum sulfide powder. The RIR value K of molybdenum sulfide (MoS2) can be used. A and the integrated intensity I of the peak near 2θ=14.4°±0.5° attributable to the (002) plane or (003) plane of molybdenum sulfide (MOS2) A , and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) B and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) is the integrated intensity I B The conversion rate R to MoS2 is obtained by the following formula (1): C .
[0103] R C (%)=(IA / K A ) / (Σ(I B / K B ))×100…(1)
[0104] Here, the RIR values may be values recorded in the inorganic crystal structure database (ICSD database), and the comprehensive powder X-ray analysis software (PDXL) (manufactured by Rigaku Corporation) may be used for analysis.
[0105] The molybdenum sulfide powder of the present invention has the following aspects.
[0106] “1” is a molybdenum sulfide powder comprising a 3R crystal structure of molybdenum disulfide.
[0107] “2” The molybdenum sulfide powder according to “1”, which is a molybdenum sulfide powder containing a 2H crystal structure and a 3R crystal structure of molybdenum disulfide,
[0108] In the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both include synthetic peaks of the 2H crystal structure and the 3R crystal structure, and the half-value width is greater than 1°.
[0109] "3" The molybdenum sulfide powder according to "1" or "2", wherein the specific surface area measured by the BET method is 10m 2 / g or more, preferably 30m 2 / g or more, more preferably 40m 2 / g or above.
[0110] "4" The molybdenum sulfide powder according to any one of "1" to "3", wherein the median particle size D is determined by a dynamic light scattering particle size distribution measuring device. 50 It is 10 nm to 1000 nm, preferably 10 nm to 600 nm, more preferably 20 nm to 500 nm, and even more preferably 40 nm to 400 nm.
[0111] "5" The molybdenum sulfide powder according to any one of "1" to "4", wherein in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is greater than 1.0, preferably greater than 1.1, and more preferably greater than 1.2.
[0112] "6" The molybdenum sulfide powder according to any one of "1" to "5", wherein the primary particles of the molybdenum sulfide particles constituting the molybdenum sulfide powder are in the shape of ropes, belts or sheets.
[0113] "7" The molybdenum sulfide powder according to any one of "1" to "6", wherein the average aspect ratio of the primary particles of the molybdenum sulfide particles constituting the molybdenum sulfide powder is 1.2 to 1200, preferably 2 to 800, more preferably 5 to 400, and even more preferably 10 to 200.
[0114] "8" The molybdenum sulfide powder according to any one of "1" to "7", wherein the conversion rate of the molybdenum sulfide powder to MoS2 is R C It is 70% or more, preferably 80% or more, and more preferably 90% or more.
[0115] <<Oxygen Reduction Catalyst>>
[0116] The molybdenum sulfide powder can be preferably used as an oxygen reduction catalyst. In addition, the molybdenum sulfide powder can also be used as an oxygen reduction catalyst by being combined with highly conductive carbon or metal.
[0117] The oxygen reduction catalyst of the present invention has the following aspects.
[0118] “11” An oxygen reduction catalyst comprising the molybdenum sulfide powder according to any one of “1” to “8”.
[0119] <<Catalyst ink>>
[0120] The catalyst ink of the present embodiment contains the above-mentioned oxygen reduction catalyst, a polymer electrolyte, and a solvent.
[0121] As the polymer electrolyte, substances commonly used in fuel cell catalyst layers can be used. Specifically, perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton conductive functional groups, and proton conductors in which phosphoric acid solutions or sulfuric acid solutions are impregnated in polymer matrices can be listed.
[0122] The solvent is not limited as long as it can disperse the oxygen reduction catalyst and the polymer electrolyte and can be applied to the working electrode substrate to form a catalyst layer. The solvent preferably contains alcohols such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, and 2-heptanol.
[0123] The catalyst ink of the present invention has the following aspects.
[0124] “21” A catalyst ink comprising an oxygen reduction catalyst including the molybdenum sulfide powder according to any one of “1” to “8”, a polymer electrolyte, and a solvent.
[0125] <<Method for producing molybdenum sulfide powder>>
[0126] The manufacturing method of this embodiment is a manufacturing method of the molybdenum sulfide powder, comprising: heating molybdenum trioxide powder at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure including molybdenum trioxide.
[0127] The molybdenum trioxide powder used in the method for producing molybdenum sulfide powder of the present embodiment contains an aggregate of primary particles having a β crystal structure of molybdenum trioxide. Compared with the conventional molybdenum trioxide powder containing only α crystals as a crystal structure, the molybdenum trioxide powder has good reactivity with sulfur, and because it contains the β crystal structure of molybdenum trioxide, the conversion rate R to MoS2 can be increased in the reaction with the sulfur source. C .
[0128] The β crystal structure of molybdenum trioxide can be confirmed by the presence of a peak attributable to the (011) plane of the β crystal of MoO3 (2θ: near 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)) in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source. The α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak at the (021) plane of the α crystal of MoO3 (2θ: near 27.32°, No. 166363 (Inorganic Crystal Structure Database, ICSD)).
[0129] Examples of the sulfur source include sulfur and hydrogen sulfide, and these may be used alone or in combination of two.
[0130] The manufacturing method of this embodiment may also include: heating molybdenum trioxide powder at a temperature of 100°C to 800°C in the absence of a sulfur source, and then heating it at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure comprising molybdenum trioxide.
[0131] The heating time in the presence of a sulfur source may be any time period as long as the sulfurization reaction proceeds sufficiently, and may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours.
[0132] In the production method of this embodiment, the average particle size of the primary particles of the molybdenum trioxide powder is preferably 5 nm to 1000 nm.
[0133] The average particle size of the primary particles of molybdenum trioxide powder refers to the average primary particle size of 50 randomly selected primary particles obtained by photographing the molybdenum trioxide powder using a scanning electron microscope (SEM), measuring the major axis (the Feret's diameter of the longest observed part) and the minor axis (the short Feret's diameter in the vertical direction relative to the Feret's diameter of the longest part) of the smallest unit particle constituting the agglomerate on the two-dimensional image (i.e., the primary particle), and taking the average value as the primary particle size.
[0134] In the method for producing molybdenum sulfide powder of the present embodiment, the charging ratio of the amount of S in the sulfur source to the amount of MoO3 in the molybdenum trioxide powder is preferably a condition for the sulfurization reaction to proceed sufficiently. The amount of S in the sulfur source is preferably 500 mol% or more, preferably 600 mol% or more, and preferably 700 mol% or more relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide powder. The amount of S in the sulfur source may be 3000 mol% or less, 2000 mol% or less, or 1500 mol% or less relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide powder.
[0135] In the production method of this embodiment, the heating temperature in the presence of the sulfur source may be any temperature at which the sulfurization reaction proceeds sufficiently, and is preferably 320°C or higher, more preferably 340°C or higher, and particularly preferably 360°C or higher. It may be 320°C to 1000°C, 340°C to 800°C, or 360°C to 600°C.
[0136] In the method for producing molybdenum sulfide powder of the present embodiment, the average particle size of the primary particles of the molybdenum trioxide powder is preferably 1 μm or less. In terms of reactivity with sulfur, it is more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. The average particle size of the primary particles of the molybdenum trioxide powder may be 10 nm or more, 20 nm or more, or 40 nm or more.
[0137] In the method for producing molybdenum sulfide powder of the present embodiment, the molybdenum trioxide powder preferably has a MoO3 content of 99.6% or more as measured by fluorescent X-ray (XRF), thereby increasing the conversion rate R to MoS2. C , it is possible to obtain molybdenum sulfide having high purity, good storage stability and no risk of generating sulfides derived from impurities.
[0138] In the method for manufacturing molybdenum sulfide powder of the present embodiment, the molybdenum trioxide powder preferably has a ratio of the peak intensity of the (011) plane attributable to the β crystal of MoO3 to the peak intensity of the (021) plane attributable to the α crystal of MoO3 (β(011) / α(021)) of 0.1 or more in a spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source.
[0139] The peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3 are respectively read with the maximum intensity of the peaks to determine the ratio (β(011) / α(021)).
[0140] In the molybdenum trioxide powder, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.
[0141] The molybdenum trioxide powder preferably has a specific surface area of 10 m 2 / g~100m 2 / g.
[0142] In the molybdenum trioxide powder, the specific surface area is preferably 10 m 2 / g or more, preferably 20m 2 / g or more, preferably 30m 2 In the molybdenum trioxide powder, the molybdenum trioxide powder preferably has a molar mass of 100 m / g or more in terms of ease of manufacture. 2 / g or less, also 90m 2 / g or less, also 80m 2 / g or less.
[0143] The molybdenum trioxide powder preferably has a ratio (I / II) of the peak intensity I due to Mo-O to the peak intensity II due to Mo-Mo in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum greater than 1.1.
[0144] The peak intensity I due to Mo-O and the peak intensity II due to Mo-Mo are read as the maximum intensities of the peaks, respectively, to obtain the ratio (I / II). The ratio (I / II) is considered to be a criterion for obtaining the β crystal structure of MoO3 in the molybdenum trioxide powder, and the larger the ratio (I / II), the better the reactivity with sulfur.
[0145] In the molybdenum trioxide powder, the ratio (I / II) is preferably 1.1 to 5.0, and may be 1.2 to 4.0, or 1.2 to 3.0.
[0146] (Method for producing molybdenum trioxide powder)
[0147] The molybdenum trioxide powder may be produced by gasifying a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and cooling the molybdenum trioxide vapor.
[0148] The method for manufacturing the molybdenum trioxide powder preferably includes: calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, gasifying the molybdenum oxide precursor compound to form molybdenum trioxide vapor, and the ratio of the metal compound to 100% by mass of the raw material mixture is less than 70% by mass in terms of oxide conversion.
[0149] The method for producing molybdenum trioxide powder can be used Figure 1 The production device 1 shown is suitably embodied.
[0150] Figure 1 1 is a schematic diagram of an example of an apparatus used in the manufacture of the molybdenum trioxide powder. The manufacturing apparatus 1 includes: a calcining furnace 2, which calcines a molybdenum oxide precursor compound or the raw material mixture to gasify the molybdenum oxide precursor compound; a cross-shaped cooling pipe 3, which is connected to the calcining furnace 2 to powderize the molybdenum trioxide vapor gasified by the calcination; and a recovery machine 4, which is a recovery unit for recovering the molybdenum trioxide powder powdered in the cooling pipe 3. At this time, the calcining furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 is provided with an opening adjustment damper 6 at the left end at the external gas intake port (not shown), and an observation window 7 is provided at the upper end. An exhaust device 8 as a first air supply unit is connected to the recovery machine 4. The exhaust device 8 exhausts air, and the recovery machine 4 and the cooling pipe 3 are sucked, and the external air is supplied to the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 exerts a suction function to passively generate air supply in the cooling pipe 3. Furthermore, the production apparatus 1 may include an external cooling device 9, whereby the cooling conditions of the molybdenum trioxide vapor generated from the calcining furnace 2 can be arbitrarily controlled.
[0151] By adjusting the opening of the damper 6, air is taken in from the external gas intake port, and the molybdenum trioxide vapor vaporized in the calcining furnace 2 is cooled in an air environment to produce molybdenum trioxide powder, thereby making the ratio (I / II) greater than 1.1, and the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide powder. In the case of using liquid nitrogen to cool the molybdenum trioxide vapor, the cooling of the molybdenum trioxide vapor in a nitrogen environment with a low oxygen concentration is likely to increase the oxygen defect density and reduce the ratio (I / II).
[0152] The molybdenum oxide precursor compound is not particularly limited as long as it is a precursor compound for forming a molybdenum trioxide powder containing an aggregate of primary particles having a β crystal structure of molybdenum trioxide.
[0153] The molybdenum oxide precursor compound is not particularly limited as long as it is a compound that forms molybdenum trioxide vapor by calcination, and examples thereof include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (H3PMo 12 O 40 ), silicomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n = 1 ~ 3)), sodium molybdate (Na2Mo n O 3n+1 (n = 1 to 3)), titanium molybdate, iron molybdate, potassium molybdate (K2Mo n O 3n+1 (n = 1 to 3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1 (n=1-3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds can be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, for example, it can be a powder such as molybdenum trioxide, or a liquid such as an ammonium molybdate aqueous solution. It is preferably a powder with good handling and energy efficiency.
[0154] As the molybdenum oxide precursor compound, it is preferred to use commercially available α-crystal molybdenum trioxide. In addition, when ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted into thermodynamically stable molybdenum trioxide by calcination, so the vaporized molybdenum oxide precursor compound becomes the above molybdenum trioxide.
[0155] Among these molybdenum oxide precursor compounds, it is preferred to contain molybdenum trioxide from the viewpoint of facilitating control of the purity, average particle size of primary particles, and crystal structure of the obtained molybdenum trioxide powder.
[0156] Molybdenum trioxide vapor may also be formed by calcining a raw material mixture including a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0157] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, aluminum compounds, silicon compounds, titanium compounds, and magnesium compounds are preferably used.
[0158] The molybdenum oxide precursor compound and the metal compound other than the molybdenum oxide precursor compound may generate an intermediate. Even in such a case, the intermediate is decomposed by calcination to vaporize molybdenum trioxide in a thermodynamically stable form.
[0159] As the metal compound other than the molybdenum oxide precursor compound, among these, aluminum compounds are preferably used to prevent damage to the calcining furnace, and metal compounds other than the molybdenum oxide precursor compound may not be used to increase the purity of the molybdenum trioxide powder.
[0160] Examples of the aluminum compound include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, diaspore, pseudodiaspore, transition aluminas (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, and mixed aluminas having two or more crystal phases.
[0161] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is calcined, the content ratio of the molybdenum oxide precursor compound relative to 100 mass % of the raw material mixture is preferably 40 mass % to 100 mass %, or may be 45 mass % to 100 mass %, or may be 50 mass % to 100 mass %.
[0162] The calcination temperature also varies depending on the molybdenum oxide precursor compound, metal compound, desired molybdenum trioxide powder, etc. used, but is generally preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, the calcination temperature is preferably 500° C. to 1500° C., more preferably 600° C. to 1550° C., and even more preferably 700° C. to 1600° C., in order to form aluminum molybdate as an intermediate.
[0163] The calcination time is not particularly limited, and may be, for example, 1 min to 30 h, 10 min to 25 h, or 100 min to 20 h.
[0164] The heating rate also varies depending on the molybdenum oxide precursor compound used, the metal compound, and the desired properties of the molybdenum trioxide powder, but from the perspective of manufacturing efficiency, it is preferably 0.1°C / min to 100°C / min, more preferably 1°C / min to 50°C / min, and even more preferably 2°C / min to 10°C / min.
[0165] The internal pressure in the calcining furnace is not particularly limited, and may be either positive pressure or reduced pressure, but from the viewpoint of appropriately discharging the molybdenum oxide precursor compound from the calcining furnace to the cooling pipe, calcination is preferably carried out under reduced pressure. As a specific degree of reduced pressure, preferably -5000Pa to -10Pa, more preferably -2000Pa to -20Pa, and further preferably -1000Pa to -50Pa. If the degree of reduced pressure is above -5000Pa, high air tightness and mechanical strength of the calcining furnace will not be excessively required, and the manufacturing cost can be reduced, so it is preferred. On the other hand, if the degree of reduced pressure is below -10Pa, clogging of the molybdenum oxide precursor compound at the discharge port of the calcining furnace can be prevented, so it is preferred.
[0166] Furthermore, when blowing gas into the calcining furnace during calcination, the temperature of the blown gas is preferably 5°C to 500°C, more preferably 10°C to 100°C.
[0167] In addition, the blowing speed of the gas is preferably 1 L / min to 500 L / min, more preferably 10 L / min to 200 L / min, relative to a calcining furnace having an effective volume of 100 L.
[0168] The temperature of the vaporized molybdenum trioxide vapor also varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200° C. to 2000° C., and more preferably 400° C. to 1500° C. Furthermore, if the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or less, it tends to be easily powdered by the supply of external air (0° C. to 100° C.) in the cooling pipe.
[0169] The discharge rate of the molybdenum trioxide vapor discharged from the calcining furnace can be controlled by the amount of the molybdenum oxide precursor compound used, the amount of the metal compound, the temperature of the calcining furnace, the air supply of the gas into the calcining furnace, and the diameter of the exhaust port of the calcining furnace. Although it also varies depending on the cooling capacity of the cooling pipe, the discharge rate of the molybdenum trioxide vapor from the calcining furnace to the cooling pipe is preferably 0.001 g / min to 100 g / min, and more preferably 0.1 g / min to 50 g / min.
[0170] The content of molybdenum trioxide vapor contained in the gas exhausted from the calcining furnace is preferably 0.01 mg / L to 1000 mg / L, more preferably 1 mg / L to 500 mg / L.
[0171] Next, the molybdenum trioxide vapor is cooled and powdered.
[0172] The cooling of the molybdenum trioxide vapor is carried out by keeping the cooling pipe at a low temperature. At this time, as a cooling method, there can be listed: cooling by sending air to the cooling pipe as described above, cooling by a cooling mechanism possessed by the cooling pipe, cooling by an external cooling device, etc.
[0173] The cooling of the molybdenum trioxide vapor is preferably carried out in an air environment. By cooling the molybdenum trioxide vapor in an air environment to prepare molybdenum trioxide powder, the ratio (I / II) can be made greater than 1.1, and the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide powder.
[0174] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably -100°C to 600°C, more preferably -50°C to 400°C.
[0175] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably 100°C / s to 100,000°C / s, more preferably 1,000°C / s to 50,000°C / s. Furthermore, the faster the cooling rate of the molybdenum trioxide vapor, the more likely it is to obtain a molybdenum trioxide powder with a smaller particle size and a larger specific surface area.
[0176] When the cooling method is cooling by sending air into the cooling pipe, the temperature of the sent air is preferably -100°C to 300°C, more preferably -50°C to 100°C.
[0177] In addition, the gas blowing speed is preferably 0.1 m 3 / min~20m 3 / min, more preferably 1m 3 / min~10m 3 / min. If the air supply speed of the gas is 0.1m 3 / min or more, a high cooling rate can be achieved, and clogging of the cooling pipe can be prevented, so it is preferred. On the other hand, if the gas supply speed is 20m 3 / min or less, an expensive first air supply unit (exhaust fan, etc.) is not required, and the manufacturing cost can be reduced, which is preferred.
[0178] The powder obtained by cooling the molybdenum trioxide vapor is transported to a recovery machine for recovery.
[0179] In the method for producing the molybdenum trioxide powder, the powder obtained by cooling the molybdenum trioxide vapor may be calcined again at a temperature of 100° C. to 320° C.
[0180] That is, the molybdenum trioxide powder obtained by the method for manufacturing the molybdenum trioxide powder can also be calcined again at a temperature of 100°C to 320°C. The calcination temperature of the re-calcination can be 120°C to 280°C, or 140°C to 240°C. The calcination time of the re-calcination can be, for example, 1 min to 4 h, 10 min to 5 h, or 100 min to 6 h. However, by re-calcining, part of the β crystal structure of molybdenum trioxide disappears. If calcined at a temperature above 350°C for 4 hours, the β crystal structure in the molybdenum trioxide powder disappears, the ratio (β(011) / α(021)) becomes 0, and the reactivity with sulfur is impaired.
[0181] The method for producing molybdenum sulfide powder of the present invention has the following aspects.
[0182] “31” A method for manufacturing molybdenum sulfide powder, manufacturing the molybdenum sulfide powder according to any one of “1” to “8”, comprising: heating molybdenum trioxide powder at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure comprising molybdenum trioxide.
[0183] “32” A method for manufacturing molybdenum sulfide powder, manufacturing the molybdenum sulfide powder according to any one of “1” to “8”, comprising: heating molybdenum trioxide powder at a temperature of 100°C to 800°C in the absence of a sulfur source, and then heating it at a temperature of 200°C to 1000°C in the presence of a sulfur source, wherein the molybdenum trioxide powder contains an aggregate of primary particles having a β crystal structure comprising molybdenum trioxide.
[0184] "33" A method for producing molybdenum sulfide powder according to "31" or "32", wherein the average particle size of the primary particles of the molybdenum trioxide powder is 5 nm to 1000 nm, preferably greater than 10 nm and less than 600 nm, more preferably greater than 20 nm and less than 400 nm, and further preferably greater than 40 nm and less than 200 nm.
[0185] "34" A method for producing molybdenum sulfide powder according to any one of "31" to "33", wherein the amount of S in the sulfur source is 500 mol% or more, preferably 600 mol% or more, and more preferably 700 mol% or more, relative to 100 mol% of MoO3 in the molybdenum trioxide powder.
[0186] "35" A method for producing molybdenum sulfide powder according to any one of "31" to "34", wherein the heating temperature in the presence of the sulfur source is above 320°C, preferably 320°C to 1000°C, more preferably 340°C to 800°C, and even more preferably 360°C to 600°C.
[0187] <<Heavy Metal Adsorbent>>
[0188] The heavy metal adsorbent of the present embodiment contains molybdenum sulfide particles, and the median particle size D of the molybdenum sulfide particles determined by a dynamic light scattering particle size distribution analyzer is 50 The heavy metal adsorbent of this embodiment has a large adsorption capacity for heavy metals and a small adsorption capacity for mineral components. The large adsorption capacity for heavy metals is considered to be due to the median particle size D of the molybdenum sulfide particles. 50 The selective adsorption performance of heavy metals, which is greater than the adsorption capacity of mineral components, is believed to be caused by the fact that sulfur in molybdenum sulfide has the property of being easily adsorbed to heavy metals.
[0189] Heavy metals that can be adsorbed by the heavy metal adsorbent of this embodiment include lead, iron, mercury, silver, gold, platinum, palladium, copper, chromium, cadmium, vanadium, manganese, cobalt, nickel, zinc, tin, tellurium, thallium, tantalum, uranium and the like. The heavy metal adsorbent of this embodiment has particularly excellent adsorption performance for heavy metals such as lead, mercury, silver and gold.
[0190] Examples of mineral components that are difficult to adsorb to a heavy metal adsorbent include calcium, potassium, sodium, and magnesium.
[0191] The median particle size D of the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment obtained by a dynamic light scattering particle size distribution analyzer is 50 The median particle size D of the molybdenum sulfide particles is preferably 10 nm to 1000 nm, and in terms of the above-mentioned effect, is preferably 600 nm or less, more preferably 500 nm or less, and particularly preferably 400 nm or less. 50 The thickness may be greater than 10 nm, greater than 20 nm, or greater than 40 nm.
[0192] The molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment preferably contain a 3R crystal structure of molybdenum disulfide. By including the 3R crystal structure, the edge portion of the crystal of the molybdenum sulfide particles increases, and the ion adsorption sites increase, which is considered to contribute to further improvement of the adsorption performance of heavy metals. In addition, by including the 3R crystal structure, the adsorption performance of heavy metals, especially lead, mercury, silver and gold, is significantly improved. It is presumed that the reason is derived from the specific surface area of the nanostructure of the molybdenum sulfide particles.
[0193] Furthermore, the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment preferably contain 2H crystal structure and 3R crystal structure of molybdenum disulfide. Generally, commercially available molybdenum disulfide particles contain many molybdenum disulfide particles with a particle size exceeding 1 μm, and are hexagonal solids, such as Figure 4As shown in FIG. 1 , as a crystal structure, it has only a 2H crystal structure. In contrast, the molybdenum sulfide particles produced by the "method for producing molybdenum sulfide particles" described later contain a 2H crystal structure and a 3R crystal structure, and the median particle size D can be easily 50 Adjust to 10nm~1000nm.
[0194] Furthermore, the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment preferably have a spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, and the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of the 2H crystal structure and the 3R crystal structure, and the half-value width is 1° or more. Furthermore, the molybdenum sulfide particles may also contain a crystal structure other than the 2H crystal structure and the 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.
[0195] The aspect that the molybdenum sulfide particles contain a 3R crystal structure having a metastable structure can be distinguished by the fact that, in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks (broad peaks) of the 2H crystal structure and the 3R crystal structure.
[0196] The specific surface area of the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment measured by the BET method is preferably 10 m 2 / g or more, more preferably 30m 2 / g or more, particularly preferably 40 m 2 The specific surface area of the molybdenum sulfide particles measured by the BET method may be 300 m 2 / g or less, also 200m 2 / g or less, also 100m 2 / g or less.
[0197] The specific surface area of the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment measured by the BET method is as large as 10 m 2 / g or more of a heavy metal adsorbent can increase the contact area with the heavy metal, so it is considered that the adsorption performance for heavy metals is improved.
[0198] In the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum of the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.
[0199] Regardless of whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo-S is roughly the same due to the covalent bond, so in the extended X-ray absorption fine structure (EXAFS) spectrum at the K absorption end of molybdenum, the intensity of the peak caused by Mo-S is the same.
[0200] On the other hand, the 2H crystal structure of molybdenum disulfide is hexagonal, so the same hexagon is located directly below the 90° hexagon of the Mo atom, so the distance between Mo-Mo becomes closer, resulting in a stronger peak intensity II of Mo-Mo.
[0201] On the contrary, the 3R crystal structure of molybdenum disulfide is rhombohedral, so the hexagon exists not directly below 90° of the hexagon, but deviates from the half angle, so the distance between Mo-Mo becomes longer, resulting in the weakening of the peak intensity II of Mo-Mo.
[0202] In the pure 2H crystal structure of molybdenum disulfide, the ratio (I / II) becomes smaller, but as the 3R crystal structure is included, the ratio (I / II) becomes larger.
[0203] In the 3R crystal structure, the hexagons of the Mo atoms in the three layers are offset from each other by half of the hexagon. Therefore, compared with the 2H crystal structure in which the hexagons of the Mo atoms in the two layers are arranged perpendicularly and regularly, the interaction between the layers is small, and it is expected that heavy metals can be easily adsorbed.
[0204] It is believed that the presence of molybdenum trioxide has an adverse effect on the heavy metal adsorption performance, so the conversion rate R of the molybdenum sulfide particles to MoS2 in the heavy metal adsorbent of this embodiment is C It is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more.
[0205] The molybdenum sulfide particles in the heavy metal adsorbent of this embodiment are converted into MoS2 by the conversion rate R C The heavy metal adsorption performance can be made better than other molybdenum disulfide raw materials and their precursors that can produce or contain molybdenum trioxide as a by-product.
[0206] The conversion rate R of the molybdenum sulfide particles to MoS2 in the heavy metal adsorbent of this embodiment is C The conversion rate R of the molybdenum sulfide powder to MoS2 C Calculate in the same way.
[0207] The heavy metal adsorbent of this embodiment can be configured to adsorb, remove or recover heavy metal ions, heavy metals or heavy metal compounds contained in a heavy metal-containing solution, such as a heavy metal-containing aqueous solution. In addition, the heavy metal adsorbent of this embodiment can be configured to adsorb, remove or recover heavy metals or heavy metal compounds contained in a heavy metal-containing gas.
[0208] The heavy metal adsorbent of the present invention has the following aspects.
[0209] "41" A heavy metal adsorbent, which is a heavy metal adsorbent containing molybdenum sulfide particles, wherein the median particle size D of the molybdenum sulfide particles is determined by a dynamic light scattering particle size distribution measuring device. 50 It is 10 nm to 1000 nm, preferably 10 nm to 600 nm, more preferably 20 nm to 500 nm, and even more preferably 40 nm to 400 nm.
[0210] "42" A heavy metal adsorbent according to "41", wherein the specific surface area of the molybdenum sulfide particles measured by the BET method is 10 m 2 / g or more, preferably 30m 2 / g or more, more preferably 40m 2 / g or above.
[0211] "43" A heavy metal adsorbent according to "41" or "42", wherein in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the molybdenum sulfide particles at the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is greater than 1.0, preferably greater than 1.1, and more preferably greater than 1.2.
[0212] "44" A heavy metal adsorbent according to any one of "41" to "43", wherein the molybdenum sulfide particles contain a 3R crystal structure of molybdenum disulfide.
[0213] “45” The heavy metal adsorbent according to “44”, wherein the molybdenum sulfide particles comprise a 2H crystal structure and a 3R crystal structure of molybdenum disulfide,
[0214] In the spectrum of the molybdenum sulfide particles obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of the 2H crystal structure and the 3R crystal structure, and the half-value width is greater than 1°.
[0215] "46" A heavy metal adsorbent according to "44" or "45", wherein the primary particles of the molybdenum sulfide particles are in the shape of ropes, belts or sheets.
[0216] "47" A heavy metal adsorbent according to any one of "44" to "46", wherein the average aspect ratio of the primary particles of the molybdenum sulfide particles is 1.2 to 1200, preferably 2 to 800, more preferably 5 to 400, and even more preferably 10 to 200.
[0217] "48" A heavy metal adsorbent according to any one of "44" to "47", wherein the conversion rate of the molybdenum sulfide particles to MoS2 is R C It is 70% or more, preferably 80% or more, and more preferably 90% or more.
[0218] (Method for producing molybdenum sulfide particles in heavy metal adsorbent)
[0219] The molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment can be produced, for example, by heating molybdenum trioxide particles having an average primary particle size of 5 nm to 1000 nm at a temperature of 200° C. to 1000° C. in the presence of a sulfur source.
[0220] The average particle size of the primary particles of molybdenum trioxide particles refers to the average primary particle size of 50 randomly selected primary particles obtained by photographing the molybdenum trioxide particles using a scanning electron microscope (SEM), measuring the major axis (the observed longest Feret's diameter) and the minor axis (the short Feret's diameter in the perpendicular direction relative to the Feret's diameter of the longest part) of the smallest unit particle (i.e., the primary particle) constituting the agglomerate on the two-dimensional image, and taking the average value as the primary particle size.
[0221] The molybdenum trioxide particles used in the production of the molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment are preferably aggregates of primary particles containing a β crystal structure of molybdenum trioxide. The molybdenum trioxide particles are preferably molybdenum trioxide powder used in the production method of the molybdenum sulfide powder.
[0222] The molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment can be produced from the molybdenum trioxide powder by the same method as described in the method for producing the molybdenum sulfide powder.
[0223] By using the method for producing molybdenum trioxide powder, it is possible to produce molybdenum trioxide particles suitable for producing molybdenum sulfide particles in the heavy metal adsorbent of the present embodiment.
[0224] <<Photothermal conversion materials>>
[0225] The photothermal conversion material of this embodiment includes a material containing molybdenum sulfide particles, and generates heat by absorbing light energy. The photothermal conversion material of this embodiment contains molybdenum sulfide particles, and therefore has exceptionally excellent light absorption performance compared to known light absorption particles such as titanium nitride and carbon black. The photothermal conversion material of this embodiment has particularly high sunlight energy absorption performance.
[0226] The photothermal conversion material of the present embodiment may be a material including molybdenum sulfide particles, a material in the form of molybdenum sulfide particles dispersed in a liquid, or a material in the form of molybdenum sulfide particles supported on a carrier.
[0227] The material in the form of molybdenum sulfide particles dispersed in a liquid will be described in detail below. Note that the present invention is not limited to the embodiments described below.
[0228] <Light-absorbing fluid>
[0229] In the photothermal conversion material of the present embodiment, the material containing the molybdenum sulfide particles is a light-absorbing fluid containing a liquid and the molybdenum sulfide particles dispersed in the liquid.
[0230] In the photothermal conversion material of this embodiment, the main component of the liquid may be water. The so-called main component of the liquid is water means that the proportion of water in the liquid is 50% by mass or more. The proportion of water in the liquid is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 90% by mass or more.
[0231] In terms of exhibiting significant light absorption performance compared to a liquid in which molybdenum sulfide particles are not dispersed, the photothermal conversion material of the present embodiment preferably contains 0.01% by mass or more of the molybdenum sulfide particles, more preferably 0.05% by mass or more, and further preferably 0.1% by mass or more, relative to the photothermal conversion material. The photothermal conversion material of the present embodiment may contain 5.0% by mass or less of the molybdenum sulfide particles, 1.0% by mass or less, or 0.5% by mass or less, relative to the light absorbing fluid. The photothermal conversion material of the present embodiment preferably contains 0.01% by mass or more and 5.0% by mass or less of the molybdenum sulfide particles, more preferably 0.05% by mass or more and 1.0% by mass or less, and further preferably 0.1% by mass or more and 0.5% by mass or less, relative to the light absorbing fluid.
[0232] The photothermal conversion material of this embodiment absorbs the irradiated light energy. The photothermal conversion material of this embodiment contains molybdenum sulfide particles, so compared with known light absorbing particles such as titanium nitride and carbon black, the light absorption performance is particularly excellent. The photothermal conversion material of this embodiment has particularly high sunlight energy absorption performance.
[0233] The photothermal conversion material of this embodiment does not require additional light absorption and heat generation components, and the photothermal conversion material itself can efficiently absorb light energy and store it in the form of heat energy. Therefore, for example, a simple device structure in which the photothermal conversion material of this embodiment flows into a transparent flow path such as a transparent tube under sunlight can be used to efficiently collect solar energy.
[0234] (Molybdenum sulfide particles)
[0235] As the molybdenum sulfide particles in the photothermal conversion material of this embodiment, commercially available molybdenum sulfide particles can be used. Compared with existing light absorbers, molybdenum sulfide particles are particularly preferred to absorb the wavelength portion (500nm to 700nm) with high energy of sunlight compared to other substances. The photothermal conversion material of this embodiment can absorb light energy more efficiently and store it in the form of heat energy by nano-sizing the molybdenum sulfide particles.
[0236] Specifically, the median particle size D of the molybdenum sulfide particles in the photothermal conversion material of the present embodiment is obtained by a dynamic light scattering particle size distribution measuring apparatus. 50 (hereinafter sometimes referred to as "median particle size D 50 ”) is preferably 10 nm to 1000 nm. In terms of large surface area and excellent light absorption performance, it is preferably 600 nm or less, more preferably 500 nm or less, and particularly preferably 400 nm or less. The median particle size D of the molybdenum sulfide particles in the photothermal conversion material of this embodiment is 50 The thickness may be greater than 10 nm, greater than 20 nm, or greater than 40 nm.
[0237] The specific surface area of the molybdenum sulfide particles in the photothermal conversion material of the present embodiment measured by the BET method is preferably 10 m 2 / g or more, more preferably 30m 2 / g or more, particularly preferably 40 m 2 The larger the specific surface area of the molybdenum sulfide particles in the photothermal conversion material of this embodiment, the better the light absorption performance can be. The specific surface area of the molybdenum sulfide particles in the photothermal conversion material of this embodiment measured by the BET method can be 300m 2 / g or less, also 200m 2 / g or less, also 100m 2 / g or less.
[0238] In the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum of the molybdenum sulfide particles in the photothermal conversion material of the present embodiment, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.
[0239] The molybdenum sulfide particles in the photothermal conversion material of the present embodiment include the 3R crystal structure of molybdenum disulfide.
[0240] In addition, the molybdenum sulfide particles in the photothermal conversion material of the present embodiment preferably contain 2H crystal structure and 3R crystal structure of molybdenum disulfide, and in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of 2H crystal structure and 3R crystal structure, and the half-value width is 1° or more. Furthermore, the molybdenum sulfide particles may also contain a crystal structure other than 2H crystal structure and 3R crystal structure of molybdenum disulfide, such as 1H crystal structure.
[0241] The molybdenum sulfide particles in the photothermal conversion material of the present embodiment include a 3R crystal structure with a metastable structure, and therefore it is believed that the light absorption performance is more excellent. Generally, commercially available molybdenum disulfide particles are molybdenum sulfide with a 2H crystal structure. In contrast, the molybdenum sulfide particles in the photothermal conversion material of the present embodiment include a 3R crystal structure with a metastable structure, which can be distinguished by the following: in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, the peak near 39.5° and the peak near 49.5° both include a synthetic peak of the 2H crystal structure and the 3R crystal structure.
[0242] In the molybdenum sulfide particles in the photothermal conversion material of the present embodiment, the shape of the molybdenum sulfide in the two-dimensional image taken by a transmission electron microscope (TEM) may be particulate, spherical, plate-like, needle-like, ribbon-like or rope-like in visual observation or image photographs, and these shapes may also be included in combination. The shape of the molybdenum sulfide is preferably rope-like, and the shape of 50 primary particles of molybdenum sulfide is preferably, on average, a length (vertical) × width (horizontal) = 50nm ~ 1000nm × 3 ~ 100nm in the range of size, more preferably a size in the range of 100nm ~ 500nm × 5 ~ 50nm, and particularly preferably a size in the range of 150nm ~ 400nm × 10 ~ 20nm. By being rope-like, the specific surface area of the molybdenum sulfide particles can be increased. Here, the so-called rope-like refers to a slender shape. The aspect ratio of the primary particles of molybdenum sulfide, that is, the value of (length (vertical)) / (width (horizontal)) is preferably 1.2 to 1200, more preferably 2 to 800, further preferably 5 to 400, and particularly preferably 10 to 200, when averaged over 50 particles.
[0243] The conversion rate R of the molybdenum sulfide particles to MoS2 in the photothermal conversion material of this embodiment is C It is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more.
[0244] The molybdenum sulfide particles in the photothermal conversion material of this embodiment are converted into MoS2 by the conversion rate R C Large, can make the light absorption performance excellent.
[0245] The conversion rate R of the molybdenum sulfide particles to MoS2 in the photothermal conversion material of this embodiment is C The conversion rate R of the molybdenum sulfide powder to MoS2 C Calculate in the same way.
[0246] (Method for producing molybdenum sulfide particles in photothermal conversion materials)
[0247] The molybdenum sulfide particles in the photothermal conversion material of the present embodiment can be produced by heating molybdenum trioxide particles at a temperature of 200° C. to 1000° C. in the presence of a sulfur source, wherein the molybdenum trioxide particles include aggregates of primary particles having a β crystal structure of molybdenum trioxide.
[0248] The molybdenum trioxide particles used in the production of the molybdenum sulfide particles in the photothermal conversion material of the present embodiment are preferably aggregates of primary particles containing a β crystal structure of molybdenum trioxide. The molybdenum trioxide particles are preferably molybdenum trioxide powder used in the production method of the molybdenum sulfide powder.
[0249] The molybdenum sulfide particles in the photothermal conversion material of the present embodiment can be produced from the molybdenum trioxide powder by the same method as described in the method for producing the molybdenum sulfide powder.
[0250] The molybdenum trioxide particles suitable for producing the molybdenum sulfide particles in the photothermal conversion material of the present embodiment can be produced by the method for producing the molybdenum trioxide powder.
[0251] The photothermal conversion material of the present invention has the following aspects.
[0252] “51” A photothermal conversion material, comprising a material containing molybdenum sulfide particles, which generates heat by absorbing light energy.
[0253] "52" The photothermal conversion material according to "51", wherein the median particle size D of the molybdenum sulfide particles is determined by a dynamic light scattering particle size distribution measuring device. 50 It is 10 nm to 1000 nm, preferably 10 nm to 600 nm, more preferably 20 nm to 500 nm, and even more preferably 40 nm to 400 nm.
[0254] "53" The photothermal conversion material according to "51" or "52", wherein the specific surface area of the molybdenum sulfide particles measured by the BET method is 10 m 2 / g or more, preferably 30m2 / g or more, more preferably 40m 2 / g or above.
[0255] “54” A photothermal conversion material according to any one of “51” to “53”, wherein in the radial distribution function of the molybdenum sulfide particles obtained by the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum, the ratio (I / II) of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo is greater than 1.0, preferably greater than 1.1, and more preferably greater than 1.2.
[0256] "55" The photothermal conversion material according to any one of "51" to "54", wherein the molybdenum sulfide particles contain a 3R crystal structure of molybdenum disulfide.
[0257] “56” The photothermal conversion material according to “55”, wherein the molybdenum sulfide particles comprise a 2H crystal structure and a 3R crystal structure of molybdenum disulfide,
[0258] In the spectrum of the molybdenum sulfide particles obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 39.5° and the peak near 49.5° both contain synthetic peaks of the 2H crystal structure and the 3R crystal structure, and the half-value width is greater than 1°.
[0259] "57" The photothermal conversion material according to "55" or "56", wherein the primary particles of the molybdenum sulfide particles are in the shape of ropes, belts or sheets.
[0260] "58" The photothermal conversion material according to any one of "55" to "57", wherein the average aspect ratio of the primary particles of the molybdenum sulfide particles is 1.2 to 1200, preferably 2 to 800, more preferably 5 to 400, and even more preferably 10 to 200.
[0261] "59" A photothermal conversion material according to any one of "55" to "58", wherein the conversion rate of the molybdenum sulfide particles to MoS2 is R C It is 70% or more, preferably 80% or more, and more preferably 90% or more.
[0262] “60” The photothermal conversion material according to any one of “51” to “59”, wherein the material containing the molybdenum sulfide particles is a light-absorbing fluid containing a liquid and the molybdenum sulfide particles dispersed in the liquid.
[0263] "61" The photothermal conversion material according to "60", wherein the main component of the liquid is water.
[0264] "62" The photothermal conversion material according to "60" or "61", wherein the molybdenum sulfide particles are contained in an amount of 0.01 mass % or more relative to the light absorbing fluid.
[0265] <<Distillation method>>
[0266] The distillation method of this embodiment evaporates the liquid by irradiating the light absorbing fluid of the photothermal conversion material with sunlight to heat the liquid.
[0267] At this time, the photothermal conversion material does not generate heat uniformly as a whole, but it is considered that a very small number of individual molybdenum sulfide particles, as a volume occupied in the light-absorbing fluid, generate heat extremely locally and become high temperature. Therefore, even if the temperature of the light-absorbing fluid as a whole is lower than the boiling point of the liquid in which the molybdenum sulfide particles are dispersed, liquid vapor is generated from the region. A part of the generated vapor reaches the surface of the light-absorbing fluid before condensing and is released to the outside of the light-absorbing fluid. That is, by irradiating the light-absorbing fluid with sunlight for heating, a larger amount of liquid vapor can be generated compared to the case where the liquid is heated by irradiating sunlight alone. Therefore, the distillation method of this embodiment can distill at a lower temperature and in a shorter time than before, and the energy utilization efficiency of sunlight is improved.
[0268] In the distillation method of this embodiment, by nano-sizing the molybdenum sulfide particles, light energy can be absorbed more efficiently, and a better liquid vapor generation effect can be exerted. Specifically, the embodiment described in the photothermal conversion material can be adopted.
[0269] The distillation method of this embodiment can be compared with the previous one, and can concentrate or remove specific components in the solution by generating steam, such as distillation of seawater or sewage at a low temperature. In this application specification, these processes are all included in distillation. The energy utilization efficiency of such distillation can be improved. Furthermore, the heat energy for distillation can be supplied only from sunlight, or part of the heat energy can be supplied from other heat sources. For example, the liquid to be distilled can be heated to the distillation temperature mainly by using heat from other heat sources, and sunlight is used as the main energy source for maintaining distillation.
[0270] The distillation method of the present invention has the following aspects.
[0271] "71" A distillation method, comprising heating the photothermal conversion material according to any one of "60" to "62" by irradiating the material with sunlight to evaporate the liquid.
[0272] Example
[0273] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.
[0274] [Method for measuring the average particle size of primary particles of molybdenum trioxide powder]
[0275] The molybdenum trioxide particles constituting the molybdenum trioxide powder were photographed using a scanning electron microscope (SEM). The major diameter (the observed longest Feret diameter) and minor diameter (the short Feret diameter in the perpendicular direction relative to the longest Feret diameter) of the smallest unit of the aggregate (i.e., primary particles) on the two-dimensional image were measured, and the average value was taken as the primary particle size. The same operation was performed on 50 randomly selected primary particles, and the average particle size of the primary particles was calculated based on the average value of the primary particle sizes of the primary particles.
[0276] [Purity determination of molybdenum trioxide: XRF analysis]
[0277] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku Co., Ltd.), about 70 mg of the sample of the recovered molybdenum trioxide powder was taken on filter paper and covered with a polypropylene (PP) film for composition analysis. The molybdenum content obtained from the XRF analysis results was converted to molybdenum trioxide (mass %) relative to 100 mass % of the molybdenum trioxide powder.
[0278] [Crystal structure analysis: XRD method]
[0279] The recovered molybdenum trioxide powder or its sulfide sample was filled to a depth of 0.5 mm in a measurement sample holder, and placed in a wide-angle X-ray diffraction (XRD) device (Ultima IV manufactured by Rigaku Co., Ltd.) and measured under the conditions of Cu / Kα rays, 40 kV / 40 mA, a scanning speed of 2° / min, and a scanning range of more than 10° and less than 70°.
[0280] [Specific surface area measurement: BET method]
[0281] The sample of molybdenum trioxide powder or molybdenum sulfide powder was measured using a specific surface area meter (BELSORP-mini manufactured by Microtrac BEL), and the surface area per 1 g of the sample measured based on the amount of nitrogen adsorption was calculated by the BET method as the specific surface area (m 2 / g).
[0282] [Conversion rate to MoS2 R C ]
[0283] The black powder of molybdenum sulfide powder was subjected to X-ray diffraction (XRD) measurement. Next, the RIR value K of molybdenum sulfide (MoS2) was used by the RIR (reference intensity ratio) method. Aand the integrated intensity I of the peak near 2θ=14.4°±0.5° attributable to the (002) plane or (003) plane of molybdenum sulfide (MOS2) A , and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) B and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) is the integrated intensity I B The conversion rate R to MoS2 is obtained by the following formula (1): C .
[0284] R C (%)=(I A / K A ) / (Σ(I B / K B ))×100…(1)
[0285] Here, the RIR values were the values listed in the Inorganic Crystal Structure Database (ICSD), and the analysis was performed using the comprehensive powder X-ray analysis software (PDXL) (manufactured by Rigaku Corporation).
[0286] [Extended X-ray Absorption Fine Structure (EXAFS) Measurement]
[0287] Use a mortar to mix 36.45 mg of molybdenum sulfide powder and 333.0 mg of boron nitride. 123.15 mg of the mixture was measured and compressed into φ8 mm tablets to obtain a measurement sample. Using the measurement sample, the extended X-ray absorption fine structure (EXAFS) was measured by transmission method using BL5S1 of the Aichi Synchrotron Light Center. Athena (Internet <Uniform Resource Locator (uniformresource locator, URL): https: / / bruceravel.github.io / demeter / >) was used for the analysis.
[0288] [The median particle size D of the molybdenum sulfide particles constituting the molybdenum sulfide powder 50 Determination of
[0289] 0.1 g of molybdenum sulfide powder was added to 20 cc of acetone, and ultrasonic treatment was performed in an ice bath for 4 hours. Then, the concentration was appropriately adjusted to a measurable range of a dynamic light scattering particle size distribution measuring device (Nanotrac Wave II manufactured by Microtrac BEL) using acetone to obtain a measurement sample. Using the measurement sample, a particle size distribution in the range of 0.0001 μm to 10 μm was measured using a dynamic light scattering particle size distribution measuring device (Nanotrac Wave II manufactured by Microtrac BEL), and the median particle size D was calculated. 50 .
[0290] Among them, for the median particle size D 50 For those exceeding 10 μm (Comparative Examples 1 and 2), the solution was adjusted in the same manner, and the particle size distribution in the range of 0.015 μm to 500 μm was measured by a laser diffraction particle size distribution measuring apparatus (SALD-7000 manufactured by Shimadzu Corporation), and the median particle size D was calculated. 50 .
[0291] [Method for observing the particle shape of molybdenum sulfide powder]
[0292] Molybdenum sulfide particles constituting the molybdenum sulfide powder were photographed using a transmission electron microscope (JEM1400 manufactured by JEOL Ltd.), and 50 primary particles within the field of view of the two-dimensional image were observed to determine whether they were in the form of ropes, bands, or flakes.
[0293] <Example 1>
[0294] (Manufacturing of molybdenum trioxide powder containing β crystal structure)
[0295] 1 kg of transition alumina (manufactured by Wako Pure Chemical Industries, Ltd., activated alumina, average particle size 45 μm) and 1 kg of molybdenum trioxide (manufactured by Sun Mining Co., Ltd.) were mixed and then loaded into a sagger. Figure 1 The calcining furnace 2 in the manufacturing device 1 shown is calcined at a temperature of 1100°C for 10 hours. During the calcination, external air is introduced from the side and bottom of the calcining furnace 2 (air supply rate: 50L / min, external air temperature: 25°C). After the molybdenum trioxide evaporates in the calcining furnace 2, it is cooled near the recovery machine 4 and precipitated in the form of particles. As the calcining furnace 2, a roller hearth kiln (RHK) simulator (manufactured by Noritake Company Limited) is used, and as the recovery machine 4, a VF-5N dust collector (manufactured by Amano Co., Ltd.) is used.
[0296] After calcination, 1.0 kg of alumina in the form of blue powder was taken out from the sagger, and 0.85 kg of molybdenum trioxide powder was recovered by the recovery machine 4. The average particle size of the primary particles of the recovered molybdenum trioxide powder was 80 nm, and the purity of molybdenum trioxide was confirmed to be 99.7% by fluorescent X-ray (XRF) measurement. The specific surface area (SA) of the molybdenum trioxide powder measured by the BET method was 44.0 m 2 / g.
[0297] In addition, the X-ray diffraction (XRD) of the molybdenum trioxide powder was measured. The result of the X-ray diffraction pattern is shown together with the standard pattern of the α crystal and the standard pattern of the β crystal of molybdenum trioxide. Figure 2 In the experiment, the peaks of α crystals and β crystals belonging to MoO3 were observed, but no other peaks were observed. Then, the peak intensity ratio (β(011) / α(021)) of the (011) plane of the β crystal (2θ: around 23.01°, No.86426 (Inorganic Crystal Structure Database (ICSD))) and the (021) plane of the α crystal (2θ: around 27.32°, No.166363 (Inorganic Crystal Structure Database (ICSD))) was calculated, and the result was that β(011) / α(021) was 5.2.
[0298] (Manufacturing of molybdenum sulfide powder)
[0299] 32.76 mg of the molybdenum trioxide powder and 333.0 mg of boron nitride were mixed in a mortar. 121.92 mg of the mixture was weighed and compressed into a tablet of φ8 mm, and the extended X-ray absorption fine structure (EXAFS) was measured. The extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum is shown in Figure 6 In the radial distribution function obtained from the spectrum, the ratio (I / II) of the peak intensity I due to Mo—O to the peak intensity II due to Mo—Mo was 2.0.
[0300] In a magnetic crucible, 1.00 g of the molybdenum trioxide powder and 1.57 g of sulfur powder (manufactured by Kanto Chemical Co., Ltd.) were mixed with a stirring rod in such a manner that the powder became uniform, and calcined at 500° C. for 4 hours in a nitrogen environment to obtain a black powder. Here, the amount of S in the sulfur powder was 705 mol% relative to the amount of MoO3 in the molybdenum trioxide powder of 100 mol%. The results of the X-ray diffraction (XRD) pattern of the black powder (molybdenum sulfide powder of Example 1) are shown together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2), and the diffraction pattern of molybdenum dioxide (MoO2) recorded in the Inorganic Crystal Structure Database (ICSD). Figure 3Molybdenum dioxide (MoO2) is a reaction intermediate.
[0301] Figure 3 In the X-ray diffraction (XRD) pattern, only the peak attributed to molybdenum disulfide (MoS2) was detected, and no peak not attributed to molybdenum disulfide (MoS2) was observed. In other words, no peak of reaction intermediates such as molybdenum dioxide (MoO2) as a by-product was observed, and only the peak attributed to molybdenum disulfide (MoS2) was observed, which confirmed that the conversion rate of the molybdenum sulfide powder of Example 1 to MoS2 was more than 99%, and the reaction with sulfur proceeded rapidly.
[0302] The crystal structure of the molybdenum sulfide powder of Example 1 was analyzed by X-ray diffraction (XRD), and it was confirmed that the powder contained a 2H crystal structure and a 3R crystal structure. The half-value widths of the peak near 39.5° and the peak near 49.5° were expanded to 2.36° and 3.71°, respectively.
[0303] The specific surface area of the molybdenum sulfide powder of Example 1 was measured by the BET method and the result was 67.8 m 2 / g.
[0304] The particle size distribution of the molybdenum sulfide powder of Example 1 was measured by a dynamic light scattering particle size distribution measuring device to obtain the median particle size D 50 , the result is 170nm.
[0305] The TEM image of the molybdenum sulfide powder of Example 1 is shown in Figure 7 A large number of molybdenum sulfides in the form of ribbons or flakes with a length of about 200 nm and a width of about 10 nm can be observed.
[0306] [Oxygen reduction reaction (ORR) activity]
[0307] 1 wt % Nafion (registered trademark) was prepared by diluting a 5 % Nafion (registered trademark) dispersion (DE520 CS type, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) with a mixed solvent of ultrapure water:1-propanol in a mass ratio of 1:1.
[0308] 2.0 mg of the molybdenum sulfide powder of Example 1 was added to a mixed solution of 100 μL of 1-hexanol and 4.1 μL of 1 wt % Nafion (registered trademark), and dispersed by ultrasonic treatment to prepare a catalyst ink.
[0309] Next, a glassy carbon rod (manufactured by Tokai Carbon Co., Ltd., φ5 mm×10 mm) was used as a substrate for a working electrode, and 5.0 μL of the dispersion liquid (catalyst ink) was applied to the glassy carbon rod, and dried at 60° C. for 1 hour to prepare a working electrode having a catalyst layer containing the molybdenum sulfide powder of Example 1. The amount of molybdenum sulfide supported on the glassy carbon rod was 0.1186 mg.
[0310] The electrochemical measurement was performed using a three-electrode cell manufactured by MICLAB Co., Ltd. and a potentiostat manufactured by Oriental Giken Co., Ltd. The electrolyte used was 0.1M H2SO4 and the measurement was performed at a temperature of 30°C. A reversible hydrogen electrode (RHE) was used as the reference electrode and a glassy carbon plate was used as the counter electrode. As a pretreatment, cyclic voltammetry was performed for 300 cycles at a scan rate of 150 mV / s and a range of 0.05V to 0.9V in a nitrogen environment.
[0311] Subsequently, low-speed scanning voltammetry (O2+4H + +4e - = >2H2O).
[0312] The ORR current density (i / mAg -1 The results are shown in Figure 4 Based on the above results, the operating voltage (vs RHE) of the working electrode having the catalyst layer containing the molybdenum sulfide powder of Example 1 was found to be 0.64V.
[0313] The extended X-ray absorption fine structure (EXAFS) of the molybdenum sulfide powder of Example 1 was measured. The extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption edge of molybdenum is shown in Fig. 9 In the radial distribution function obtained from the spectrum, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo was 1.2.
[0314] <Comparative Example 1>
[0315] As the molybdenum sulfide powder of Comparative Example 1, the oxygen reduction reaction (ORR) activity was evaluated using a molybdenum sulfide reagent manufactured by Kanto Chemical Co., Ltd. The evaluation method was the same as that of the molybdenum sulfide powder of Example 1. The results are shown in Figure 4 Based on the above results, the working voltage (vsRHE) of the working electrode obtained from the molybdenum sulfide powder of Comparative Example 1 was found to be 0.46V.
[0316] In addition, the X-ray diffraction pattern of the molybdenum sulfide reagent of Comparative Example 1 is shown together with the diffraction pattern of molybdenum sulfide having a 2H crystal structure. Figure 5 It can be seen that the molybdenum sulfide reagent of Comparative Example 1 is molybdenum sulfide with a 2H crystal structure of 99% or more. The half-value widths of the peak near 39.5° and the peak near 49.5° are narrowed to 0.23° and 0.22°, respectively.
[0317] For the molybdenum sulfide powder of Comparative Example 1, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0318] The TEM image of the molybdenum sulfide powder of Comparative Example 1 is shown in Figure 8 The particle shape is amorphous, and no rope-shaped, ribbon-shaped or flake-shaped molybdenum sulfide is observed.
[0319] <Example 2>
[0320] The molybdenum sulfide powder of Example 2 was produced in the same manner as in Example 1, except that the mixture of 1.00 g of molybdenum trioxide powder and 1.57 g of sulfur powder in Example 1 was changed to the mixture of 1.00 g of molybdenum trioxide powder and 3.14 g of sulfur powder, and the calcination of the molybdenum trioxide powder and the sulfur powder at 500° C. for 4 hours was changed to the calcination at 400° C. for 4 hours. Here, the amount of S in the sulfur powder was 1410 mol% relative to the amount of MoO3 in the molybdenum trioxide powder of 100 mol%.
[0321] In the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Example 2, only the peaks belonging to molybdenum disulfide (MoS2) were detected, and no peaks not belonging to molybdenum disulfide (MoS2) were seen. That is, no by-products were detected. It can be confirmed that the conversion rate to MoS2 is more than 99%, and the reaction with sulfur occurs rapidly. Furthermore, the crystal structure of the molybdenum sulfide powder of Example 2 was analyzed by X-ray diffraction (XRD), and the results confirmed that it contained a 2H crystal structure and a 3R crystal structure. The half-value widths of the peaks near 39.5° and 49.5° were expanded to 2.38° and 3.29°, respectively.
[0322] For the molybdenum sulfide powder of Example 2, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0323] The TEM image of the molybdenum sulfide powder of Example 2 is shown in Figure 8 A large number of rope-shaped molybdenum sulfides with a length of about 200 nm and a width of about 10 nm can be observed.
[0324] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Example 2 was evaluated in the same manner as that of the molybdenum sulfide powder of Example 1. The operating voltage (vs RHE) of the working electrode obtained from the molybdenum sulfide powder of Example 2 was found to be 0.65 V.
[0325] <Example 3>
[0326] Molybdenum sulfide powder of Example 3 was produced in the same manner as in Example 1, except that the calcination of the molybdenum trioxide powder and the sulfur powder at 500° C. for 4 hours in Example 1 was changed to calcination at 400° C. for 4 hours.
[0327] In the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Example 3, only the peaks belonging to molybdenum disulfide (MoS2) were detected, and no peaks not belonging to molybdenum disulfide (MoS2) were observed. That is, no by-products were detected. Furthermore, the crystal structure of the molybdenum sulfide powder of Example 3 was analyzed by X-ray diffraction (XRD), and the results confirmed that it contained a 2H crystal structure and a 3R crystal structure. The half-value widths of the peaks near 39.5° and 49.5° were expanded to 2.40° and 3.43°, respectively.
[0328] For the molybdenum sulfide powder of Example 3, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0329] The TEM image of the molybdenum sulfide powder of Example 3 is shown in Figure 8 A large number of rope-shaped molybdenum sulfides with a length of about 150 nm and a width of about 10 nm can be observed.
[0330] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Example 3 was evaluated in the same manner as that of the molybdenum sulfide powder of Example 1. The operating voltage (vs RHE) of the working electrode obtained from the molybdenum sulfide powder of Example 3 was found to be 0.63 V.
[0331] <Example 4>
[0332] 5.00 g of the molybdenum trioxide powder obtained in Example 1 was placed in a magnetic crucible and calcined again at 400°C for 4 hours. 1.00 g of the re-calcined molybdenum trioxide powder was mixed with 1.57 g of sulfur powder and calcined at 400°C for 4 hours in a nitrogen environment to produce a black powder, i.e., the molybdenum sulfide powder of Example 4.
[0333] The results of the crystal structure analysis of the molybdenum sulfide powder of Example 4 by X-ray diffraction (XRD) confirmed that the conversion rate to MoS2 was 90%, and the reaction with sulfur occurred rapidly. Furthermore, the crystal structure analysis of the molybdenum sulfide powder of Example 4 by X-ray diffraction (XRD) confirmed that it contained 2H crystal structure and 3R crystal structure. The half-value widths of the peak near 39.5° and the peak near 49.5° were expanded to 2.40° and 3.43°, respectively.
[0334] By XRD measurement, a peak attributed to molybdenum dioxide (MoO2) as a reaction intermediate was observed. This was indicated as "yes" as a by-product in Table 1.
[0335] For the molybdenum sulfide powder of Example 4, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0336] The TEM image of the molybdenum sulfide powder of Example 4 is shown in Figure 8 A large number of rope-shaped molybdenum sulfides with a width of about 10 nm and a length of about 200 nm can be observed.
[0337] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Example 4 was evaluated in the same manner as that of the molybdenum sulfide powder of Example 1. The operating voltage (vs RHE) of the working electrode obtained from the molybdenum sulfide powder of Example 4 was found to be 0.62 V.
[0338] <Comparative Example 2>
[0339] In a magnetic crucible, 1.00 g of molybdenum trioxide powder (MoO3) manufactured by Taiyo Mining Co., Ltd. and 1.57 g of sulfur powder (manufactured by Kanto Chemical Co., Ltd.) were mixed with a stirring rod in such a manner that the powder became uniform, and calcined at 400°C for 4 hours under a nitrogen environment to obtain a black powder. The results of the X-ray diffraction (XRD) pattern of the black powder (molybdenum sulfide powder of Comparative Example 2) are shown together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2), and the diffraction pattern of molybdenum dioxide (MoO2). Fig.10 middle.
[0340] Fig.10 In the X-ray diffraction (XRD) pattern, the peak of molybdenum disulfide (MoS2) belonging to the 2H crystal structure and the peak belonging to molybdenum dioxide (MoO2) were detected, but the peak of molybdenum disulfide (MoS2) belonging to the 3R crystal structure was not seen. The half-value widths of the peak near 39.5° and the peak near 49.5° were 1.73° and 0.82°, respectively. The molybdenum sulfide powder of Comparative Example 2 contained a reaction intermediate (MoO2), and the conversion rate to MoS2 was as low as 53%.
[0341] The molybdenum trioxide powder (MoO3) (manufactured by Taiyo Mining Co., Ltd.) used as the raw material contains only α crystal structure and does not contain β crystal structure. In addition, the average particle size of the molybdenum trioxide powder (MoO3) is as large as about 10 μm, so it is considered that the conversion rate to MoS2 is low.
[0342] For the molybdenum sulfide powder of Comparative Example 2, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0343] The TEM image of the molybdenum sulfide powder of Comparative Example 2 is shown in Figure 8 The particle shape is amorphous, and no rope-like molybdenum sulfide is observed.
[0344] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Comparative Example 2 was evaluated in the same manner as that of the molybdenum sulfide powder of Example 1. The operating voltage (vs RHE) of the working electrode obtained from the molybdenum sulfide powder of Comparative Example 2 was 0.41 V.
[0345] <Comparative Example 3>
[0346] A black powder was obtained in the same manner as in Example 1 except that the mixture of 1.00 g of molybdenum trioxide powder and 1.57 g of sulfur powder in Example 1 was changed to the mixture of 1.00 g of molybdenum trioxide powder and 0.79 g of sulfur powder, and the calcination of the molybdenum trioxide powder and the sulfur powder at 500° C. for 4 hours was changed to the calcination at 400° C. for 4 hours. Here, the amount of S in the sulfur powder was 355 mol% relative to 100 mol% of the MoO3 amount of the molybdenum trioxide powder.
[0347] The results of the X-ray diffraction (XRD) pattern of the black powder (molybdenum sulfide powder of Comparative Example 3) are shown together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2). Fig.11 middle.
[0348] Fig.11 In the X-ray diffraction (XRD) pattern, peaks of molybdenum disulfide (MoS2) belonging to the 2H crystal structure and peaks belonging to the reaction intermediate (Mo9O 25 The peaks of molybdenum disulfide (MoS2) belonging to the 3R crystal structure are not observed. The half-value widths of the peak near 39.5° and the peak near 49.5° are 2.41° and 0.50°, respectively. The molybdenum sulfide powder of Comparative Example 3 contains the reaction intermediate (Mo9O 25 and MoO2), the conversion rate to MoS2 is as low as 62%.
[0349] For the molybdenum sulfide powder of Comparative Example 3, similarly to the molybdenum sulfide powder of Example 1, the specific surface area (SA), the ratio (I / II) of the peak intensity I due to Mo-S and the peak intensity II due to Mo-Mo obtained by the extended X-ray absorption fine structure (EXAFS) measurement of the K absorption edge of molybdenum, and the median particle size D 50 The results are shown in Table 1.
[0350] The TEM image of the molybdenum sulfide powder of Comparative Example 3 is shown in Figure 8 The particle shape is amorphous, and no rope-like molybdenum sulfide is observed.
[0351] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Comparative Example 3 was evaluated in the same manner as that of the molybdenum sulfide powder of Example 1. The operating voltage (vs RHE) of the working electrode obtained from the molybdenum sulfide powder of Comparative Example 3 was 0.44V.
[0352] <Comparative Example 4>
[0353] Molybdenum sulfide powder of Comparative Example 4 was produced in the same manner as in Example 1, except that the calcination of the molybdenum trioxide powder and the sulfur powder at 500° C. for 4 hours in Example 1 was changed to calcination at 300° C. for 4 hours.
[0354] The results of the X-ray diffraction (XRD) pattern of the molybdenum sulfide powder of Comparative Example 4 are shown together with the diffraction pattern of the 3R crystal structure of molybdenum disulfide (MoS2), the diffraction pattern of the 2H crystal structure of molybdenum disulfide (MoS2) and the diffraction pattern of molybdenum dioxide (MoO2). Fig.12 middle.
[0355] Fig.12 In the X-ray diffraction (XRD) pattern, peaks belonging to molybdenum trioxide powder (MoO3) and peaks belonging to reaction intermediates (Mo9O 25 The peaks of 39.5° and 49.5°, which correspond to the peaks of molybdenum disulfide (MoS2) with 3R crystal structure and molybdenum disulfide (MoS2) with 2H crystal structure, are very small, and the half value width cannot be calculated. The molybdenum sulfide powder of Comparative Example 4 contains molybdenum trioxide powder (MoO3) and the reaction intermediate (Mo9O 25 and MoO2), the conversion rate to MoS2 is as low as 8%.
[0356] The specific surface area (SA) and the median diameter D of the molybdenum sulfide powder of Comparative Example 4 were determined in the same manner as the molybdenum sulfide powder of Example 1. 50 The results are shown in Table 1. In the TEM image of the molybdenum sulfide powder of Comparative Example 4, the particle shape was amorphous, and no rope-like molybdenum sulfide was observed.
[0357] The oxygen reduction reaction (ORR) activity of the molybdenum sulfide powder of Comparative Example 4 was evaluated in the same manner as the molybdenum sulfide powder of Example 1. The amount of current observed in the molybdenum sulfide powder of Comparative Example 4 was very small, and the operating voltage (vs RHE) of the working electrode could not be determined.
[0358] As shown in the results of Table 1, the molybdenum sulfide powders of Examples 1 to 4 are superior in oxygen reduction reaction (ORR) activity compared to the molybdenum sulfide powders of Comparative Examples 1 to 4.
[0359]
[0360] [Heavy metal adsorbent]
[0361] <Example 5>
[0362] A 0.1 mmol / L mixed aqueous solution of eight metal species, namely, lithium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, iron (III) chloride hexahydrate, nickel (II) chloride hexahydrate, and lead nitrate was prepared. All reagents were manufactured by Kanto Chemical Co., Ltd.
[0363] 1.0 mL of the mixed aqueous solution was loaded into the sample introduction part of an inductively coupled plasma (ICP) optical emission spectrometer (OES, manufactured by PerkinElmer, Optima 8300) to measure the content of each metal. The results are shown in Table 2 as the metal content of the initial solution (1).
[0364] 0.09 g of the molybdenum sulfide powder of Example 1 was added to 90 g of the initial solution (1), and the mixture was stirred for 24 hours using a Lab Shaker.
[0365] Thereafter, the stirred solution was separated by filtration, and 1.0 mL of the aqueous solution was loaded into the sample introduction part of an ICP optical emission spectrometer (ICP-OES) to measure the content of each metal. The results are shown in Table 2 as the residual metal amount.
[0366] In addition, Table 2 shows the removal rate (%) represented by the following formula.
[0367] Removal rate (%) = (metal content of initial solution (1) - metal residue) × 100 / metal content of initial solution (1)
[0368] When the calculated value of the removal rate (%) is a negative number, it is represented as 0.0%.
[0369] The heavy metal adsorbent of Example 5, which uses the molybdenum sulfide particles constituting the molybdenum sulfide powder of Example 1 as an adsorbent, has a large removal rate of Pb and Fe, and adsorbs heavy metals (Pb and Fe) with high selectivity, but has particularly excellent adsorption performance for Pb. In addition, a large amount of minerals (Na, Mg, K, Ca) are not adsorbed.
[0370] <Example 6>
[0371] 0.09 g of the molybdenum sulfide reagent of Comparative Example 1 was added to 90 g of the initial solution (1) used in Example 5, and the mixture was stirred for 24 hours using a Lab Shaker.
[0372] Thereafter, the stirred solution was separated by filtration, and 1.0 mL of the aqueous solution was loaded into the sample introduction part of an ICP optical emission spectrometer (ICP-OES) to measure the content of each metal. The results are shown in Table 2 as the residual metal amount.
[0373] In addition, Table 2 shows the removal rate (%) represented by the following formula.
[0374] Removal rate (%) = (metal content of initial solution (1) - metal residue) × 100 / metal content of initial solution (1)
[0375] When the calculated value of the removal rate (%) is a negative number, it is represented as 0.0%.
[0376] The heavy metal adsorbent of Example 6 using the molybdenum sulfide reagent of Comparative Example 1 as an adsorbent selectively adsorbed heavy metals (Pb and Fe), but had low adsorption performance for Pb. In addition, the heavy metal adsorbent of Example 6 using the molybdenum sulfide reagent of Comparative Example 1 as an adsorbent did not adsorb a large amount of minerals (Na, Mg, K, Ca).
[0377] <Comparative Example 5>
[0378] Zeolite (ZEOLUM (registered trademark) A-4 manufactured by Tosoh Corporation, spherical, 14 mesh to 20 mesh) was used as the heavy metal adsorbent of Comparative Example 5, and the following evaluation experiment was performed.
[0379] A 0.1 mmol / L mixed aqueous solution of 8 kinds of metal species was prepared in the same manner as in Example 5. All reagents manufactured by Kanto Chemical Co., Ltd. were used.
[0380] 1.0 mL of the mixed aqueous solution was loaded into the sample introduction part of an ICP optical emission spectrometer (ICP-OES) to measure the content of each metal. The results are shown in Table 2 as the metal content of the initial solution (2).
[0381] 0.09 g of the zeolite was added to 90 g of the initial solution (2), and the mixture was stirred for 24 hours using a Lab Shaker.
[0382] Thereafter, the stirred solution was separated by filtration, and 1.0 mL of the aqueous solution was loaded into the sample introduction part of an ICP optical emission spectrometer (ICP-OES) to measure the content of each metal. The results are shown in Table 2 as the residual metal amount.
[0383] In addition, Table 2 shows the removal rate (%) represented by the following formula.
[0384] Removal rate (%) = (metal content of initial solution (2) - metal residue) × 100 / metal content of initial solution (2)
[0385] When the calculated value of the removal rate (%) is a negative number, it is represented as 0.0%.
[0386] The heavy metal adsorbent (zeolite) of Comparative Example 5 strongly adsorbs heavy metals (Pb and Fe), but also adsorbs a large amount of minerals (Na, Mg, K, Ca) very well.
[0387] <Comparative Example 6>
[0388] Using activated carbon (Kuraraycoal (registered trademark) manufactured by KURARAY Co., Ltd.) as the heavy metal adsorbent of Comparative Example 6, the following evaluation experiment was performed.
[0389] 0.09 g of the activated carbon of Comparative Example 6 was added to 90 g of the initial solution (2) used in Comparative Example 5, and the mixture was stirred for 24 hours using a Lab Shaker.
[0390] Thereafter, the stirred solution was separated by filtration, and 1.0 mL of the aqueous solution was loaded into the sample introduction part of an ICP optical emission spectrometer (ICP-OES) to measure the content of each metal. The results are shown in Table 2 as the residual metal amount.
[0391] In addition, Table 2 shows the removal rate (%) represented by the following formula.
[0392] Removal rate (%) = (metal content of initial solution (2) - metal residue) × 100 / metal content of initial solution (2)
[0393] When the calculated value of the removal rate (%) is a negative number, it is represented as 0.0%.
[0394] The activated carbon of Comparative Example 6 selectively adsorbed heavy metals (Pb and Fe), but had low adsorption performance for Pb. In addition, the heavy metal adsorbent using the activated carbon of Comparative Example 6 as an adsorbent did not adsorb a large amount of minerals (Na, Mg, K, Ca).
[0395] [Table 2]
[0396]
[0397] [Heavy metal (lead) adsorption evaluation]
[0398] A reagent solution of lead (II) nitrate (manufactured by Kanto Chemical Co., Ltd.) was diluted with ion-exchanged water to adjust the diluted solution so that the heavy metal concentration was about 1000 ppb as an initial concentration.
[0399] 40 g of the diluted solution was placed in a 50 mL tube. 40 mg (0.1 wt%) of each heavy metal adsorbent of Example 5, Example 6, Comparative Example 5 and Comparative Example 6 were added thereto to prepare an experimental solution, which was stirred at a speed of 15 rpm using a Rotamix RKVSD manufactured by TOWA LABO Co., Ltd. for 3 h, 6 h, 12 h and 24 h.
[0400] After stirring, about 24 g of the test solution was syringe filtered using filter 25AS020AN manufactured by Toyo Filter Paper Co., Ltd., and about 1 g of nitric acid (density: 1.38 g / mL) (electronics grade manufactured by Kanto Chemical Co., Ltd.) was added to prepare a stabilized sample solution.
[0401] The amount of residual heavy metals in the sample solution was determined using an ICP emission spectrophotometer (ICP-OES, manufactured by PerkinElmer, Optima 8300) (standard curve method). The measured data in the sample solution was converted to the concentration of the experimental solution before dilution with nitric acid as the residual heavy metal concentration after the experiment. The results of the heavy metal (lead) adsorption evaluation are shown in Table 3. The detection limit was 50 ppb.
[0402] [Table 3]
[0403]
[0404] [Heavy metal (mercury) adsorption evaluation]
[0405] The heavy metal (mercury) adsorption evaluation was performed in the same manner as the heavy metal (lead) adsorption evaluation, except that lead (II) nitrate was replaced with mercury (II) chloride (manufactured by Kanto Chemical Co., Ltd.). The results of the heavy metal (mercury) adsorption evaluation are shown in Table 4. The detection limit was 50 ppb in all cases.
[0406] [Table 4]
[0407]
[0408] [Evaluation of heavy metal (silver) adsorption]
[0409] The heavy metal (silver) adsorption evaluation was performed in the same manner as the heavy metal (lead) adsorption evaluation, except that lead (II) nitrate was replaced with silver (I) nitrate (manufactured by Kanto Chemical Co., Ltd., silver standard solution). The results of the heavy metal (silver) adsorption evaluation are shown in Table 5. The detection limit was 10 ppb in all cases.
[0410] [Table 5]
[0411]
[0412] [Evaluation of heavy metal (gold) adsorption]
[0413] The heavy metal (gold) adsorption evaluation was performed in the same manner as the heavy metal (lead) adsorption evaluation, except that lead (II) nitrate in the heavy metal (lead) adsorption evaluation was changed to tetrachloroauric (III) acid (gold standard solution manufactured by Nacalai Tesque Co., Ltd.). The results of the heavy metal (gold) adsorption evaluation are shown in Table 6. The detection limit was 100 ppb in all cases.
[0414] [Table 6]
[0415]
[0416] [Photothermal conversion materials]
[0417] <Example 7>
[0418] 20 g of ion exchange water was poured into a 100 ml disposable cup manufactured by TERAOKA Co., Ltd., and 20 mg (0.1 mass %) of the molybdenum sulfide powder of Example 1 was added, and ultrasonic stirring was performed for 10 minutes to obtain a light absorbing fluid of the photothermal conversion material of Example 7. The surrounding of the container can be simply kept warm.
[0419] The XES-40S3 manufactured by San-Yong Electric Co., Ltd. was used as a simulated sunlight generator with a power of 1000W / m 2 The photothermal conversion material of Example 7 is irradiated with an illumination of.
[0420] After 1.5 hours from the start of irradiation, the measurement was performed, and irradiation was continued for a total of 3 hours, and then the measurement was performed again. The amount of water evaporated 1.5 hours after the steady state of the photothermal conversion material of Example 7 was calculated from the difference between the two measured values to be 3.17 g.
[0421] The laboratory environment during the time period for measuring the amount of water evaporation was 22.2°C to 22.4°C and 34% humidity.
[0422] 20 g of ion exchanged water poured into a 100 ml disposable cup manufactured by TERAOKA Co., Ltd. was measured 1.5 hours later and 3 hours later in the same laboratory environment as in Example 7 without irradiating simulated sunlight. The reference water evaporation amount calculated from the difference between the two measured values was 0.132 g.
[0423] <Example 8>
[0424] 20 g of ion exchange water was poured into a 100 ml disposable cup manufactured by TERAOKA Co., Ltd., and 20 mg (0.1 mass %) of molybdenum sulfide powder of Comparative Example 1 was added, and ultrasonic stirring was performed for 10 minutes to obtain a light absorbing fluid of the photothermal conversion material of Example 8. The surrounding of the container can be easily kept warm.
[0425] The amount of water evaporated 1.5 hours after the steady state of the photothermal conversion material of Example 8 was measured in the same manner as in Example 7. The measurement results are shown in Table 7. In addition, 20 g of ion exchange water injected into a 100 ml disposable cup manufactured by TERAOKA Co., Ltd. was not irradiated with simulated sunlight, but was measured at the same time 1.5 hours later and 3 hours later under the same laboratory environment as in Example 8. The reference water evaporation amount calculated from the difference between the two measured values is shown in Table 7. The laboratory environment when these were implemented is shown in Table 7.
[0426] <Comparative Example 7>
[0427] 20 g of ion exchange water was poured into a 100 ml disposable cup of TERAOKA Co., Ltd., and titanium nitride (TiN) particles (median particle size D 50 : 1000nm) 20mg (0.1% by mass) was added and ultrasonic stirring was performed for 10 minutes to obtain a light absorbing fluid of the photothermal conversion material of Comparative Example 7. The surrounding of the container can be simply kept warm.
[0428] The water evaporation amount 1.5 hours after the steady state of the photothermal conversion material of Comparative Example 7 was measured in the same manner as in Example 7, and the measurement results are shown in Table 7. In addition, as in Examples 7 and 8, the reference water evaporation amount and laboratory environment at this time are shown in Table 7.
[0429] <Comparative Example 8>
[0430] 20 g of ion exchange water was poured into a 100 ml disposable cup of TERAOKA Co., Ltd., and conductive carbon black (Ketjen Black (registered trademark) EC300J, median particle size D) manufactured by Lion Specialty Chemicals Co., Ltd. was added. 50 :40nm) 7.45mg (0.038% by mass) was added and ultrasonic stirring was performed for 10 minutes to obtain a light absorbing fluid of the photothermal conversion material of Comparative Example 8. The surrounding of the container can be easily kept warm.
[0431] The specific gravity of molybdenum disulfide (MoS2) is set to 5.1, and the specific gravity of the conductive carbon black (Ketjen black (registered trademark), EC300J) is set to 1.9, the same as the carbon black. The added volume amount of the conductive carbon black in Comparative Example 8 is the same as the added volume amount of molybdenum disulfide (MoS2) in Examples 7 and 8.
[0432] The water evaporation amount 1.5 hours after the steady state of the photothermal conversion material of Comparative Example 8 was measured in the same manner as in Example 7, and the measurement results are shown in Table 7. In addition, as in Examples 7 and 8, the reference water evaporation amount and laboratory environment at this time are shown in Table 7.
[0433] <Comparative Example 9>
[0434] 20 g of ion exchange water was poured into a 100 ml disposable cup of TERAOKA Co., Ltd., and conductive carbon black (Ketjen Black (registered trademark) EC300J, median particle size D) manufactured by Lion Specialty Chemicals Co., Ltd. was added. 50 :40nm) 20mg (0.1% by mass) was added and ultrasonic stirring was performed for 10 minutes to obtain a light absorbing fluid of the photothermal conversion material of Comparative Example 9. The surrounding of the container can be simply kept warm.
[0435] The water evaporation amount 1.5 hours after the steady state of the photothermal conversion material of Comparative Example 9 was measured in the same manner as in Example 7, and the measurement results are shown in Table 7. In addition, as in Examples 7 and 8, the reference water evaporation amount and laboratory environment at this time are shown in Table 7.
[0436] <Comparative Example 10>
[0437] 20 g of ion exchanged water was poured into a 100 ml disposable cup produced by TERAOKA Co., Ltd., and this was used as the light absorbing fluid of the photothermal conversion material of Comparative Example 10. The surrounding of the container can be easily kept warm.
[0438] The water evaporation amount 1.5 hours after the steady state of the photothermal conversion material of Comparative Example 10 was measured in the same manner as in Example 7, and the measurement results are shown in Table 7. In addition, as in Examples 7 and 8, the reference water evaporation amount and laboratory environment at this time are shown in Table 7.
[0439]
[0440] In the experiments of Examples 7 and 8, and Comparative Examples 7 to 10, the reference water evaporation amount of the water-only samples under each laboratory environment hardly changed, so it can be confirmed that the laboratory environments are the same and have no effect on the test results.
[0441] The experiments of Examples 7 and 8 and Comparative Examples 7 to 10 were conducted independently. The laboratory environment during the time period for measuring the water evaporation amount was within the range of temperature 21.6°C to 23.7°C and humidity 34% to 41%. At the same time, the reference water evaporation amount of the sample with only water performed under each laboratory environment was almost unchanged, so it was confirmed that the laboratory environment was the same and had no effect on the test results.
[0442] As shown in Table 7, it can be seen that the amount of water vapor in the photothermal conversion materials of Examples 7 and 8 after 1.5 hours is greater than the amount of water vapor in the photothermal conversion materials of Comparative Examples 7 to 10 after 1.5 hours, and a large amount of water vapor is generated.
[0443] As described above, the light absorbing fluid of the photothermal conversion material according to the present embodiment can evaporate the liquid faster than the case of only water without the molybdenum sulfide particles dispersed therein when the titanium nitride particles or carbon black are dispersed at a temperature lower than the boiling point of the liquid in which the molybdenum sulfide particles are dispersed. Therefore, the light absorbing fluid of the photothermal conversion material according to the present embodiment can be rapidly distilled at a lower temperature, thereby reducing energy loss during distillation.
[0444] In particular, the photothermal conversion material of Example 7 containing the molybdenum sulfide particles of Example 1 generates more water vapor and shows better light absorption performance. The median particle size D of the molybdenum sulfide particles of Example 1 is 50 The surface area is 10 nm to 1000 nm, and the specific surface area is 10 m 2 / g or more, the ratio (I / II) is greater than 1.0, and the 2H crystal structure and 3R crystal structure of molybdenum disulfide are included. It is believed that by nano-sizing the molybdenum sulfide particles, the specific surface area is increased, and the light absorption efficiency is further increased.
[0445] (Absorption spectrum measurement)
[0446] The light absorbing fluid of the photothermal conversion material of Example 7 containing molybdenum sulfide particles (MoS2) constituting the molybdenum sulfide powder of Example 1, the light absorbing fluid of the photothermal conversion material of Comparative Example 7 containing titanium nitride (TiN) particles, and the light absorbing fluid of the photothermal conversion material of Comparative Example 9 containing conductive carbon black (Ketjen Black (registered trademark), EC300J) were diluted with ion exchange water to adjust the concentration to 0.2 mg / H2Og, and after ultrasonic stirring for 1 hour, the absorption spectra at wavelengths from ultraviolet to near-infrared were measured using a spectrophotometer U-4100 manufactured by Hitachi High-Tech Science.
[0447] The results of these absorption spectra are shown together with the sunlight spectrum (AM1.5G) according to the International Electrotechnical Commission (IEC) 60904-3 (equivalent standard Japanese Industrial Standards (JIS) C8904-3). Fig.13 middle.
[0448] Molybdenum sulfide particles have high absorption in the wavelength range of 350 nm to 800 nm, which accounts for about 40% of the energy of sunlight, and are therefore excellent as a sunlight absorbing material.
[0449] Industrial Applicability
[0450] The molybdenum sulfide powder of the present invention has excellent oxygen reduction reaction (ORR) activity and can be used as an electrode material.
[0451] The heavy metal adsorbent of the present invention has a large adsorption capacity for heavy metals and a small adsorption capacity for mineral components, and can therefore be preferably used for water purification materials, soot treatment materials, heavy metal outflow prevention materials, precious metal recovery materials, and the like.
[0452] Compared with gold, carbon nanotubes, titanium nitride, etc., which are known as sunlight absorbing materials, the molybdenum sulfide particles used in the photothermal conversion material of the present invention are cheaper. The photothermal conversion material of the present invention has excellent light absorption performance, especially sunlight absorption performance, and can therefore replace thermal desalination facilities and reverse osmosis (RO) desalination facilities, and can be used in distillation methods such as irradiating sunlight for heating in drinking water generation devices for disasters.
Claims
1. A method for producing molybdenum sulfide powder, the method comprising: Molybdenum trioxide powder is heated at a temperature of 200° C. to 1000° C. in the presence of a sulfur source, wherein the molybdenum trioxide powder contains aggregates of primary particles having a β crystal structure of molybdenum trioxide. The molybdenum trioxide powder is obtained by the following steps: vaporizing a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and The vaporized molybdenum trioxide vapor is cooled in an air environment. 2 . The method for producing molybdenum sulfide powder according to claim 1 , wherein the average particle size of primary particles of the molybdenum trioxide powder is greater than or equal to 10 nm and less than or equal to 600 nm.
3. The method for producing molybdenum sulfide powder according to claim 1, wherein the amount of S in the sulfur source is 500 mol% or more relative to 100 mol% of the MoO3 amount of the molybdenum trioxide powder. 4 . The method for producing molybdenum sulfide powder according to claim 1 , wherein the heating temperature in the presence of the sulfur source is 320° C. or higher.
Citation Information
Patent Citations
Molybdenum disulfide nanoflower and its manufacturing method
JP2004277199A
Method and apparatus for the production of inorganic fullerene-like nanoparticles
JP2004512250A
Solar heat collection method and device
JP2010144957A
Composite adsorbent and method for production thereof, and water purification material and water purifier
WO2004039494A1
Preparation method of nano-molybdenum disulfide
CN103086436A